Method for controlling work function of at least one surface, electrode, electrochemical cell, energy storage device, photovoltaic cell and electrical component thereof
Through the sedimentary hand system and using the CISS effect, it solves the problem that the electrode function function in the existing technology is difficult to reduce, realize the reduction of electrode function functions and internal resistance, and improve the efficiency of electronic transfer.
Patent Information
- Application Number
- CN202380047567.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-04
- Filing Date
- 2023-05-24
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to effectively reduce the work function of the electrode, especially when manufacturing low-work function electrodes, there are problems such as high cost, high complexity and dependence on the vacuum environment.
By sedimentary hand system to control the surface skills, the use of the spinning selective effect (CISS effect) of the hand -sex molecule caused the charge and spin polarization, thereby reducing the function of the electrode.
Realize the function and internal resistance of the electrode, improve the efficiency of electronic transfer, and improve the performance of the electrochemical system.
Smart Images

Figure CN119384892A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to electrodes, electrochemical cells, energy storage devices, photovoltaic cells and electrical components. In particular, but not exclusively, the present disclosure also relates to a method for controlling the work function of at least one surface. Background Art
[0002] Listed below are references that may be considered relevant as background to the subject matter disclosed herein:
[0003] 1.Duan,J.et al.Building Safe Lithium-Ion Batteries for ElectricVehicles: A Review.Electrochemical Energy Reviews vol.3 Preprint at https: / / doi.org / 10.1007 / s41918-019-00060-4(2020).
[0004] 2.Goodenough, JBEnergy storage materials: A perspective. EnergyStorage Materials vol.1158-161 Preprint at https: / / doi.org / 10.1016 / j.ensm.2015.07.001(2015).
[0005] 3.Schipper,F.et al.Review--Recent Advances and Remaining Challenges for Lithium Ion Battery Cathodes.J Electrochem Soc 164,A6220-A6228(2017).
[0006] 4. Sun, Y Ket al. High-energy cathode material for long-life and safelithium batteries. Nat Mater 8, 320-324 (2009).
[0007] 5.Sun,Y.,Liu,N.&Cui,Y.Promises and challenges of nanomaterials forlithium-based rechargeable batteries.Nature Energy vol.1Preprint at https: / / doi.org / 10.1038 / nenergy.2016.71(2016).
[0008] 6.Lim,B.B.et al.Advanced Concentration Gradient Cathode Material withTwo-Slope for High-Energy and Safe Lithium Batteries.Adv Funct Mater 25,4673-4680(2015).
[0009] 7.Manthiram,A.,Song,B.&Li,W.A perspective on nickel-rich layeredoxide cathodes for lithium-ion batteries.Energy Storage Materials vol.6 125-139 Preprint at https: / / doi.org / 10.1016 / j.ensm.2016.10.007(2017).
[0010] 8.Manthiram,A.,Knight,J.C.,Myung,S.T.,Oh,S.M.&Sun,Y.K.Nickel-Rich andLithium-Rich Layered Oxide Cathodes:Progress and Perspectives.Adv EnergyMater 6,(2016).
[0011] 9.Liu,W.et al.Nickel-Rich Layered Lithium Transition-Metal Oxide forHigh-Energy Lithium-Ion Batteries.Angewandte Chemie 127,4518-4536(2015).
[0012] 10.Xia,Y.,Zheng,J.,Wang,C.&Gu,M.Designing principle for Ni-richcathode materials with high energy density for practical applications.NanoEnergy vol.49434-452 Preprint at https: / / doi.org / 10.1016 / j.nanoen.2018.04.062(2018).
[0013] 11.Weigel,T.et al.Structural and Electrochemical Aspects of LiNi 0.8Co 0.1 Mn 0.1 O 2 Cathode Materials Doped by Various Cations.ACS Energy Lett4,508-516(2019).
[0014] 12.Li,T.et al.Degradation Mechanisms and Mitigation Strategies ofNickel-Rich NMC-Based Lithium-Ion Batteries.Electrochemical Energy Reviewsvol.343-80Preprint at https: / / doi.org / 10.1007 / s41918-019-00053-3(2020).
[0015] 13.Deng,S.et al.Manipulation of an ionic and electronic conductiveinterface for highly-stable high-voltage cathodes.Nano Energy 65,(2019).
[0016] 14.Zhang,J.et al.Suppressing the Structure Deterioration of Ni-RichLiNi0.8Co0.1Mn0.1O2 through Atom-Scale Interfacial Integration of Self-Forming Hierarchical Spinel Layer with Ni Gradient Concentration.ACS ApplMater Interfaces 9,29794-29803(2017).
[0017] 15.Wang,H.et al.Enhanced interfacial reaction interface stability ofNi-rich cathode materials by fabricating dual-modified layer coating forlithium-ion batteries.Electrochim Acta 366,(2021).
[0018] 16.Wang,K.X.,Li,X.H.&Chen,J.S.Surface and interface engineering ofelectrode materials for lithium-ion batteries.Advanced Materials 27,527-545(2015).
[0019] 17.Kalluri,S.et al.Feasibility of Cathode Surface Coating Technologyfor High-Energy Lithium-ion and Beyond-Lithium-ion Batteries.AdvancedMaterials 29,(2017).
[0020] 18.Lin,F.et al.Surface reconstruction and chemical evolution ofstoichiometric layered cathode materials for lithium-ion batteries.Nat Commun5,3529(2014).
[0021] 19.Xu,G.L.et al.Building ultraconformal protective layers on bothsecondary and primary particles of layered lithium transition metal oxidecathodes.Nat Energy 4,484-494(2019).
[0022] 20.Cheng,X.et al.Realizing superior cycling stability of Ni-Richlayered cathode by combination of grain boundary engineering and surfacecoating.Nano Energy 62,30-37(2019).
[0023] 21.Meng,X.,Yang,X.Q.&Sun,X.Emerging applications of atomic layerdeposition for lithium-ion battery studies.Advanced Materials vol.24 3589-3615Preprint at https: / / doi.org / 10.1002 / adma.201200397(2012).
[0024] 22.Assaud,L.,Pitzschel,K.,Hanbücken,M.&Santinacci,L.Highly-ConformalTiN Thin Films Grown by Thermal and Plasma-Enhanced Atomic LayerDeposition.ECS Journal of Solid State Science and Technology 3,P253-P258(2014).
[0025] 23.Yang,H.et al.Simultaneously Dual Modification of Ni-Rich LayeredOxide Cathode for High-Energy Lithium-Ion Batteries.Adv Funct Mater 29,(2019).
[0026] 24.Kim,H.,Kim,M.G.,Jeong,H.Y.,Nam,H.&Cho,J.A new coating method foralleviating surface degradation of LiNi0.6Co0.2Mn0.2O2 cathode material:Nanoscale surface treatment of primary particles.Nano Lett 15,2111-2119(2015).
[0027] 25.Sun,H.H.et al.Transition metal-doped Ni-rich layered cathodematerials for durable Li-ion batteries.Nat Commun 12,(2021).
[0028] 26.Tian,C.,Lin,F.&Doeff,M.M.Electrochemical Characteristics ofLayered Transition Metal Oxide Cathode Materials for Lithium Ion Batteries:Surface,Bulk Behavior,and Thermal Properties.Acc Chem Res 51,89-96(2018).
[0029] 27.Kim,J.et al.Self-Induced Concentration Gradient in Nickel-RichCathodes by Sacrificial Polymeric Bead Clusters for High-Energy Lithium-IonBatteries.Adv Energy Mater 7,(2017).
[0030] 28.Li,S.et al.An effective approach to improve the electrochemicalperformance of LiNi0.6Co0.2Mn0.2O2 cathode by an MOF-derived coating.J MaterChem A Mater 4,5823-5827(2016).
[0031] 29.Sun,D.,Sun,F.,Deng,X.&Li,Z.Mixed-Metal Strategy on Metal-OrganicFrameworks(MOFs)for Functionalities Expansion:Co Substitution Induces AerobicOxidation of Cyclohexene over Inactive Ni-MOF-74.Inorg Chem 54,8639-8643(2015).
[0032] 30.G.T.Babcock,How oxygen is activated and reduced in respiration.Proc.Natl.Acad.Sci.U.S.A.96,12971-12973(1999).
[0033] 31.S.M.M.Ehteshami,S.H.Chan,The role of hydrogen and fuel cells tostore renewable energy in the future energy network-potentials andchallenges.Energy Policy 73,103-109(2014).
[0034] 32.A.Bauen,F.Foradini,D.Hart,“Fuel cell-based renewable energysupply:sustainable energy for isolated and island communities”in New andRenewable Technologies for Sustainable Development,N.H.Afgan,M.da Carvalho,Eds.(Springer,Boston,2002),pp.421-428.
[0035] 33.S.Ferguson-Miller,G.T.Babcock,Heme / copper terminaloxidases.Chem.Rev.96,2889-2908(1996).
[0036] 34.P.J.Silva,Refining the reaction mechanism of O2 towards its co-substrate in cofactor-free dioxygenases.PeerJ 4,e2805(2016).
[0037] 35.L.Gabison,C.Chopard,N.Colloc'h,F.Peyrot,B.Castro,M E.Hajji,M.Altarsha,G.Monard,M.Chiadmi,T.Prangé,X-ray,ESR,and quantum mechanicsstudies unravel a spin well in the cofactor-less urate oxidase.Proteins 79,1964-1976(2011).
[0038] 36.A.Kulkarni,S.Siahrostami,A.Patel,J.K. Understandingcatalytic activity trends in the oxygen reduction reaction.Chem.Rev.118,2302-2312(2018).
[0039] 37.J.K. J.Rossmeisl,A.Logadottir,L.Lindqvist,Origin of theoverpotential for oxygen reduction at a fuel-cell cathode.J.Phys.Chem.B 108,17886-17892(2004).
[0040] 38.Z.W.Seh,J.Kibsgaard,C.F.Dickens,I.Chorkendorff,J.K. T.F.Jaramillo,Combining theory and experiment in electrocatalysis:Insightsinto materials design.Science 355,eaad4998(2017).
[0041] 39.Supriya Ghosh,Suryakant Mishra,Eytan Avigad,Brian P.Bloom,L.T.Baczewski,Shira Yochelis,Yossi Paltiel,Ron Naaman,David H.Waldeck,Effectof Chiral Molecules on the Electron’s Spin Wavefunction at Interfaces,J.Phys.Chem.Lett.11,1550-1557(2020).
[0042] 40.Naaman,R.&Waldeck,D.H.Chiral-induced spin selectivityeffect.Journal of Physical Chemistry Letters 3,2178-2187(2012).
[0043] 41.Naaman,R.&Waldeck,D.H.Spintronics and chirality:Spin selectivityin electron transport through chiral molecules.Annual Review of PhysicalChemistry vol.66 263-281 Preprint at https: / / doi.org / 10.1146 / annurev-physchem-040214-121554(2015).
[0044] 42.Naaman,R.,Paltiel,Y.&Waldeck,D.H.Chiral molecules and the electronspin.Nature Reviews Chemistry vol.3 250-260 Preprint at https: / / doi.org / 10.1038 / s41570-019-0087-1(2019).
[0045] 43.Evers,F.etal.Theory of Chirality Induced Spin Selectivity:Progressand Challenges.Advanced Materials vol.34 Preprint at https: / / doi.org / 10.1002 / adma.202106629(2022).
[0046] 44.Kumar,A.et al.Chirality-induced spin polarization places symmetryconstraints on biomolecular interactions.Proc Natl Acad Sci U S A 114,2474-2478(2017).
[0047] 45.Michaeli,K.,Kantor-Uriel,N.,Naaman,R.&Waldeck,D.H.The electron’sspin and molecular chirality-how are they related and how do they affect lifeprocesses?Chemical Society Reviews vol.456478-6487 Preprint at https: / / doi.org / 10.1039 / c6cs00369a(2016).
[0048] 46.Metzger,T.S.et al.The Electron Spin as a Chiral Reagent.AngewandteChemie 132,1670-1675(2020).
[0049] 47.Ghosh,S.et al.Effect of Chiral Molecules on the Electron’s SpinWavefunction at Interfaces.Journal of Physical Chemistry Letters 11,1550-1557(2020).
[0050] 48.Michaeli,K.&Naaman,R.Origin of Spin-Dependent Tunneling ThroughChiral Molecules.Journal of Physical Chemistry C 123,17043-17048(2019).
[0051] 49.Ziv,A.et al.AFM-Based Spin-Exchange Microscopy Using ChiralMolecules.Advanced Materials 31,(2019).
[0052] 50.Roushan,P.et al.Topological surface states protected frombackscattering by chiral spin texture.Nature 460,1106-1109(2009).
[0053] 51.Mtangi,W.et al.Control of Electrons’Spin Eliminates HydrogenPeroxide Formation during Water Splitting.J Am Chem Soc 139,2794-2798(2017).
[0054] 52.Kapon,Y.et al.Evidence for new enantiospecific interaction forcein chiral biomolecules.Chem 7,2787-2799(2021).
[0055] 53.Mtangi,W.,Kiran,V.,Fontanesi,C.&Naaman,R.Role of the Electron SpinPolarization in Water Splitting.Journal of Physical Chemistry Letters 6,4916-4922(2015).
[0056] 54.Zhang,W.,Banerjee-Ghosh,K.,Tassinari,F.&Naaman,R.EnhancedElectrochemical Water Splitting with Chiral Molecule-Coated Fe3O4Nanoparticles.ACS Energy Lett 3,2308-2313(2018).
[0057] 55.R.Naaman,Y.Paltiel,D.Waldeck,Chiral molecules and the electron’sspin.Nat.Rev.Chem.3,250-260(2019).
[0058] 56.D.Mishra,T.Z.Markus,R.Naaman,M.Kettner,B. H.Zacharias,N.Friedman,M Sheves,C.Fontanesi,Spin-dependent electron transmission throughbacteriorhodopsin embedded in purple membrane.Proc.Natl.Acad.Sci.U.S.A.110,14872-14876(2013).
[0059] 57.S.Mishra,S.Pirbadian,A.K.Mondal,M.Y.E1-Naggar,R.Naaman,Spin-dependent electron transport through bacterial cell surface multihemeelectron conduits.J.Am.Chem.Soc.141,19198-19202(2019).
[0060] 58.Y.Nie,L.Li,Z.Wei,Recent advancements in Pt and Pt-free catalystsfor oxygen reduction reaction.Chem.Soc.Rev.44,2168-2201(2015).
[0061] 59.Saha,A.et al.Improved Cycling Stability of LiNi0.8Co0.1Mn0.1O2Cathode Material via Variable Temperature Atomic Surface Reduction withDiethyl Zinc.Small 18,(2022).
[0062] 60.Paula Yurkanis Bruice.Organic Chemistry.(Prentice Hall,2001).
[0063] 61.Ahn,J.&Yim,T.Ni-rich LiNi0.8Co0.1Mn0.1O2 oxide functionalized byallyl phenyl sulfone as high-performance cathode material for lithium-ionbatteries.JAlloys Compd 867,(2021).
[0064] 62.D.Wang,X.Pan,P.Yang,R.Li,H.Xu,Y.Li,F.Meng,J.Zhang,M.An,Transitionmetal and nitrogen Co-doped carbon-based electrocatalysts for the oxygenreduction reaction:from active site insights to the rational design ofprecursors and structures.ChemSusChem 14,33-55(2021).
[0065] 63.X.Ge,A.Sumboja,D.Wuu,T.An,B.Li,F.T.Goh,T.A.Hot,Y.Zong,Z.Liu,Oxygenreduction in alkaline media:from mechanisms to recent advances ofcatalysts.ACS Catal.5,4643-4667(2015).
[0066] 64.X.Yang,J.Nash,N.Oliveira,Y.Yan,B.Xu,Understanding the pHdependence of underpotential deposited hydrogen onplatinum.Angew.Chem.Int.Ed.58,17718-17723(2019).
[0067] 65.I.Meirzada,N.Sukenik,G.Haim,S.Yochelis,L.T.Baczewski,Y.Paltiel,N.Bar-Gill,Long-timescale magnetization ordering induced by an adsorbedchiral monolayer on ferromagnets.ACS Nano 15,5574-5579(2021).
[0068] 66.D.H.Waldeck,R.Naaman,Y.Paltiel,The spin selectivity effect inchiral materials.APL Mater.9,040902(2021).
[0069] 67.S.Mishra,A.K.Mondal,S.Pal,T.K.Das,E Z.Smolinsky,G.Siligardi,R.Naaman,Length-dependent electron spin polarization in oligopeptides andDNA.J.Phys.Chem.C 124,10776-10782(2020).
[0070] 68.M.Shao,Q.Chang,J.P.Dodelet,R.Chenitz,Recent advances inelectrocatalysts for oxygen reduction reaction.Chem.Rev.116,3594-3657(2016).
[0071] 69.J.Kim,A.A.Gewirth,Mechanism of oxygen electroreduction on goldsurfaces in basic media.J.Phy.Chem.B 110,2565-2571(2006).
[0072] 70.J.Fransson,Vibrational origin of exchange splitting and chiral-induced spin selectivity.Phys.Rev.B 102,235416(2020).
[0073] 71.J.Fransson,Charge redistribution and spin polarization driven bycorrelation induced electron exchange in chiral molecules.Nano Lett.21,3026-3032(2021).
[0074] 72.Z.Zeng,T.Zhang,Y.Liu,W.Zhang,Z.Yin,Z.Ji,J.Wei,Magnetic field-enhanced 4-electron pathway for well-aligned Co3O4 / electrospun carbonnanofibers in the oxygen reduction reaction,ChemSusChem 11,580-588(2018).
[0075] 73.B.F.Minaev,Spin effects in reductive activation of O2 by oxydaseenzymes.RIKEN Rev.44,147-149(2002).
[0076] 74.H E.Lee,H Y.Ahn,J.Mun,YYLee,M.Kim,NHCho,K.Chang,WSKim,J.Rho,KTNam,Amino-acid-and peptide-directed synthesis of chiral plasmonic goldnanoparticles.Nature 556,360-365(2018).
[0077] Acknowledgment herein of the above references should not be inferred as meaning that these references are in any way relevant to the patentability of the subject matter disclosed herein.
[0078] background
[0079] The work function of the surface of any material (solid or liquid) is defined as the minimum energy required to move an electron from the inside of the material to infinity. If contaminants or coatings are present, the work function measured for a specific material will change. There are various methods for measuring the work function of a surface, such as photoelectron spectroscopy, where electrons are injected from the material with a well-defined photon energy and the energy of the electron is determined. Another method is the Kelvin probe. The Kelvin probe is a non-contact, non-destructive measurement device. It is based on a vibrating capacitor and measures the surface potential difference between the investigation surface and a vibrating reference surface.
[0080] A large number of charge storage devices (such as thin film batteries) and electronic devices (such as organic thin film optoelectronic devices including organic light emitting diodes (OLEDs), organic thin film transistors (TFTs) or organic solar cells (OSCs)) require at least one electrode material that exhibits a work function that is low enough to inject electrons into or collect electrons from the lowest unoccupied molecular orbital (LUMO).
[0081] As far as materials with low work functions are concerned, a variety of metals, such as, for example, Li, Na, Mg, Ca or Zn, represent suitable candidates for such electrodes. However, low work function electrode layers are usually applied using thermal evaporation or sputtering, which are expensive, complex and not easily applicable to many metals, such as Zn. Furthermore, these electrodes must be processed in a high vacuum and require precision equipment due to the high reactivity of pure metals to air and water.
[0082] Different strategies have been proposed to solve at least some of these problems. For example, Zhou et al., Science 2012, 336 (2) 327-336 discloses that the work function of a conductor can be reduced by modifying the surface of the conductor with polyethylene imine, which allows the use of an alternative electrode material that is less prone to oxidation. However, the method requires additional manufacturing steps, and it is still difficult to achieve a work function as low as that of a pure alkali metal by using this method. An alternative method is adopted in US 2005 / 0019976. In this article, an electrodeposition and printing technique that does not require a vacuum environment is disclosed. In addition, WO 2008 / 127111 proposes a method for manufacturing an electrode by electrodeposition, wherein a plating solution containing an ionic liquid and a metal or metalloid ion is applied so that the latter is reduced and deposited to form an electrode on the surface of an electroactive material. However, these methods require a drying step and a fine treatment of the formed electrode under an inert gas atmosphere to avoid contact with air and water. Furthermore, the possible device configurations obtainable by these methods are limited in terms of electrode arrangement, since deposition of a solution processed layer on top of the electrode material (or alternatively deposition of the electrode on top of the solution processed layer) is either not possible or results in an inhomogeneous and degraded electrode layer due to the reactivity of the electrode material to residual solvents (e.g. water). WO 2013 / 019993 relates to a method for enhancing charge injection by providing an isopotential source layer comprising non-reducible mobile ions.
[0083] Lithium-ion batteries (LIBs) are the most common type of electrochemical energy storage and are used in a variety of industries, including electric vehicles, phones, portable electronics, and stationary grid power stations [1, 2]. They are known for their high energy density, reliability, and efficiency [3-6]. Nickel-rich layered lithium transition metal oxides are promising cathode materials for next-generation LIBs used in automotive applications due to their high specific capacity (200 mAh / g-250 mAh / g), high operating voltage (about 3.6 V-3.8 V), good rate capability, and relatively low cost [7-9]. Active LiNi 0.8 Co 0.1 Mn 0.1 The chiral organic coating of O2(NCM811) material enhances the discharge capacity and rate performance and reduces the material retention rate.
[0084] However, these materials can suffer from structural and interfacial instabilities during repeated charge and discharge, leading to performance degradation and safety issues. One issue is that highly active materials can accelerate the decomposition of the electrolyte, leading to rapid capacity decay and overall poor battery performance [7, 10]. Internal resistance and overpotential also play a key role in battery performance. Low resistance leads to higher power density and reduced risk of overheating, while low overpotential leads to higher energy density
[11] .
[0085] Due to the presence of high Ni content in NCM811 cathode materials operating at higher cut-off voltages (>4.4 V vs. Li+ / Li), capacity fading and relatively poor rate performance become serious effects
[12] . The important causes of capacity fading can be attributed to structural degradation induced by: (i) the accumulation of NiO phase on the surface, (ii) lithium residues on the surface, which can easily absorb H2O and CO2 to produce Li2CO3 and LiOH, resulting in high pH and high interfacial resistance of the cathode material, and (iii) the most important factor of continuous electrochemical reactions during charge-discharge, which induce the formation of parasitic byproduct HF in the electrolyte, which dissolves transition metal ions on the NCM material [13, 14]. Undesirable transition metal dissolution from the cathode can destroy the structural stability of the cathode active material and change the composition of the solid electrolyte interface (SEI)
[15] .
[0086] It is therefore not surprising that significant efforts have been reported in the literature to target reduction of degradation and enhancement of battery performance. A promising approach utilizes surface modification of cathode materials through coating processes [16, 17]. This approach aims to address the capacity fade of Ni-rich cathode materials during prolonged charge-discharge cycles. Protective surface modification includes both cathode surface coating and anode surface coating using core-shell structure designs through wet chemical methods
[18] , physical vapor deposition
[19] , chemical vapor deposition
[20] , atomic layer deposition [21, 22]. Surface treatment can protect the contact between NCM cathode materials and electrolytes, inhibit transition metal dissolution from the cathode and reduce side reactions to improve electrochemical performance in terms of rate capability, specific capacity retention and long-term cycling [23, 24]. In addition, coating can reduce microcracks and oxygen release, which are associated with these changes after prolonged charge and discharge cycles and pose safety risks.
[0087] This approach has been widely studied in lithium-ion batteries, which have stable transition metals, metal oxides (such as Al2O3, SiO2, TiO2, ZnO, ZrO2), phosphates (AlPO4, Li3PO4) and fluorides (AlF3) [25,26], polymer materials
[27] and metal organic frameworks (MOFs) [28,29] protected on the cathode material to resist the corrosion of the cathode material by avoiding direct electrode-electrolyte contact and HF during long-term charge-discharge cycles. However, most of these inorganic coating materials have poor conductivity and parasitic byproduct formation with lithium and cathode materials, which show an adverse (antipathetic) effect on the electrochemical performance. In addition, most of these coating materials are Li + Ionic insulators that inhibit Li + The ions diffuse in the cathode material and therefore its full capacity cannot be utilized.
[0088] Controlled oxygen reduction reaction (ORR) is crucial for aerobic life
[29] and the development of clean energy technologies such as fuel cells[31,32]. The process starts with oxygen in the triplet ground state and ends with all products in the singlet state. Therefore, the spin constraints in oxygen reduction must be overcome. Typically, this has been accomplished by using electrodes with large spin-orbit coupling (SOC).
[0089] Understanding the detailed mechanism of ORR is challenging because spin selection rules must be considered: the ground state of diatomic oxygen is in a triplet electron state The reaction product is in a closed-shell singlet state. In fact, current fuel cell technology uses rare metal catalysts that possess significant spin-orbit coupling. In contrast, aerobic organisms carry out the ORR without the need for precious metals. Although some enzymes possess metal cofactors with significant spin-orbit coupling (which can relax the spin constraints in the reaction)
[33] , enzymes without metal cofactors are known to promote efficient reduction of oxygen [34,35]. It seems clear that important subtleties of the biochemical mechanism remain elusive.
[0090] The intrinsic activity of ORR catalysts has not been significantly improved, and there has been limited success in developing catalysts with lower overpotentials
[36] . The best ORR catalysts are platinum-based, and the adsorption of oxygen on the catalyst is very efficient at low reduction potentials, so proton and electron transfer is inefficient. Only at high reduction potentials can the reaction proceed due to the reduced stability of the adsorbed oxygen [37,38]. This has been suggested to be the origin of the observed ORR overpotential and a key bottleneck in catalyst development.
[0091] General Description
[0092] There is a need to provide a method for preparing a surface with a low work function. In particular, there is a need to provide an inexpensive and simple method for preparing a low work function electrode, which can be used to manufacture a wide variety of device configurations. This enables, among other things, electronic devices and / or charge storage devices with improved charging times to be provided.
[0093] The subject matter disclosed herein relates to a new technology for controlling the work function of a surface by depositing a chiral system. Chirality is a property of an object that cannot be superimposed on its mirror image, much like the left and right hands. Chiral molecules are essential in chemistry and biology because they can have different properties and reactivity compared to their mirror images [44, 45]. The term "chiral system" refers to molecules with non-superimposable mirror images (i.e., enantiomers) hereinafter. A chiral system can be chiral at the molecular level (intrinsically chiral) or chiral due to the formation of a structure of several molecules (each molecule itself is not intrinsically chiral). In some embodiments, it can include homochiral molecules or unidirectional chiral molecules, in which all chiral molecules in a given sample have the same chirality or handedness (e.g., left-handed or right-handed, but not a mixture of the two). A surface or a portion of a surface is made of a chiral material or coated with a chiral material. It has been found that chemically binding a chiral system to a surface or physically adsorbing a surface with a film of a chiral material (molecule or inorganic material) changes the surface work function. This allows electrons to leave or enter the surface at a lower potential than leaving or entering another surface (such as a bare electrode or an electrode coated with an achiral film). Thus, utilizing chiral coatings on surfaces makes it possible to reduce their work function. As described above, adsorption of molecules on a surface changes their work function due to a change in the dipole moment perpendicular to the surface. In addition to a simple change in dipole moment, the presence of chiral molecules induces spin polarization in the magnetized substrate, resulting in a preference for electron transfer with a single spin and less resistance at the substrate-molecule interface, as described in
[39] .
[39] describes Kelvin probe measurements on ferromagnetic thin film electrodes coated with a self-assembled monolayer of chiral molecules, revealing that the penetration of electrons from a metal electrode into a chiral molecule depends on the magnetization direction of the ferromagnet and the chirality of the molecule. The change in work function in the magnetic electrode described in
[39] is due to a change in the orientation of the magnet of the electrode. However, the use of magnetic or ferromagnetic electrodes in electrochemical systems is impractical, being expensive and very limited in terms of fabrication with respect to a variety of device configurations. Furthermore, despite the change in the work function of the magnetic electrode, the use of a magnetic or ferromagnetic coated electrode does not allow electrons to leave or enter the magnetic or ferromagnetic coated electrode at a lower potential and / or resistance than leaving or entering the uncoated magnetic electrode.
[0094] The unique approach of the present inventors involves molecular chiral coatings, which are known to enable pure spin currents due to the chirality-induced spin selectivity (CISS) effect [40-43]. The CISS effect is a phenomenon in which the spin state of electrons passing through a chiral molecule is selectively affected by the handedness of the molecule [40, 42, 46, 47]. In other words, the spin of an electron passing through a left-handed molecule is different from the spin state of an electron passing through a right-handed molecule [30, 32]. Therefore, charge displacement and transport in chiral molecules produce a spin-polarized electron distribution [48, 49]. Spin-polarized electrons cannot backscatter in the chiral potential, and therefore the resistance is reduced
[50] . Electron spin is also critical in chemical reactions in which most bonds are in the singlet state [51, 52]. However, the oxygen molecule is special, having a triplet state at the ground state energy level
[51] . Therefore, the standard oxidation process is spin-forbidden and has a large overpotential. In these cases, the CISS effect can be exploited to align multiple electron spins, enabling the efficiency of these processes to be improved
[53] , as will be described in more detail below with respect to the oxygen reduction reaction. Similarly, spin alignment can be exploited to increase the use of spin-selective currents in electrolyzers and fuel cells, improving their efficiency. In fact, the present inventors have demonstrated that the use of chiral molecules as intermediates in water splitting can improve efficiency by reducing the overpotential by 50% [53, 54]. In the present disclosure, the electrochemical properties of chiral L-α-helical polyalanine (AHPA), [H]-C(AAAAAK)7-[OH], achiral 12-mercaptododecanoic acid (MDA), and pristine cathode materials, all purchased from Sigma Aldrich, Ltd. Israel, were compared. The chiral molecules coated the active material, and the results indicated an increase in specific capacitance at both low charge and discharge rates and high charge and discharge rates using the chiral coating. Specifically, the AHPA chirally coated NCM811 cathode material improved the efficiency by 6%, lowered the overpotential during the reduction process by 0.1 V, and reduced energy loss and heating barriers.
[0095] The present disclosure presents a technology for reducing the internal resistance and work function of a surface and improving the electron transfer efficiency. This can be achieved by providing an electrode and a coating for an electrode made of or coated with a chiral material. The presence of chiral molecules induces electron spin polarization, resulting in more efficient transfer of electrons with a single spin and less resistance at the interface. The inventors of the present disclosure provide novel electrodes and coatings for electrodes and electrode components, which show improved electron transfer efficiency.
[0096] The technology can be used to enhance the operation of any of the following devices: batteries, electrolyzers, fuel cells, switches, connectors, electrochemical capacitors, photovoltaic (PV) cells, and devices where the Schottky barrier should be controlled. Chiral molecules and chiral organic and inorganic films can be used to control the electrode-electrolyte interface in electrochemical systems, thereby adjusting the surface work function and / or spin state at the electrode-electrolyte interface to optimize the operation of the electrochemical system.
[0097] According to another aspect of the present disclosure, a method for controlling the work function of at least one surface is provided, the method comprising: measuring a first work function of a first surface; depositing a chiral system on the first surface to cause a change in a specific first work function; applying a potential difference between the first surface and the second surface to generate a charge transfer between the first surface and the second surface; measuring a second work function of the first surface carrying the chiral system; wherein the second work function is lower than the first work function. The interaction between the chiral system and the first surface is configured to cause a spatial rearrangement of charges on the first surface, a spin polarization of the first surface, and a spin polarization of electrons injected from or into the first surface, thereby changing the work function of the first surface, allowing electrons to leave or enter the first surface with a lower potential energy and / or reducing the resistance of the first surface to be lower than the resistance of the first surface before the chiral system is deposited.
[0098] In some embodiments, depositing the chiral system on the first surface comprises chemically binding the chiral system to the first surface or physically adsorbing the chiral system on the first surface.
[0099] In some embodiments, when the first surface at least partially carrying the chiral system is configured and operable as a working electrode and the second surface is configured and operable as a counter electrode, the method further comprises, prior to applying the potential difference, interacting at least one of the chiral-coated surfaces with an electrolyte to function as an electrode and interacting the other surface with an electrolyte to function as a counter electrode. The interaction between the chiral electrode and the electrolyte is configured to change the spin state at the electrode-electrolyte interface.
[0100] In some embodiments, the method further comprises immersing at least one electrode and the counter electrode in an electrolyte prior to applying the potential difference, the interaction between the chiral electrode and the electrolyte being configured to change the spin state at the electrode-electrolyte interface.
[0101] According to another broad aspect of the present disclosure, an electrode for an electrochemical process is provided. The electrode includes a substrate having a conductive surface carrying a chiral system, wherein the chiral system is configured to control the work function of the electrode. The interaction between the chiral system and the electrode is configured to cause charge rearrangement, spin polarization of the conductive surface, and spin polarization of electrons injected from or into the conductive surface, so as to reduce the work function of the electrode and the electrical potential energy for starting the electrochemical process and the electrical internal resistance of the electrode.
[0102] The chiral system may include at least one of an organic substance and an inorganic substance having chiral properties or any combination thereof. The chiral system may include a chiral polymer and / or a chiral inorganic film. The chiral system may be configured as a single layer structure or a multilayer structure, which operates as a layer to improve charge separation. It may also include a self-assembled monolayer of chiral molecules or chiral biomolecules. The chiral system may be chemically bonded to the surface of a substrate or physically adsorbed on the surface of a substrate. The substrate may be made of at least one of a metal, a chiral conductor, and a semiconductor.
[0103] In some embodiments, the chiral system includes at least one of the following chiral organic materials or the following chiral inorganic materials, the chiral organic materials are: polypeptides, oligopeptides, amino acids, proteins, DNA, helicene, chiral polymers, small chiral molecules or any combination thereof, the chiral inorganic materials are: chiral oxides, chiral metals and chiral crystals or any combination thereof. The term "small chiral molecule" refers to a molecule having a thickness of less than 10 nm.
[0104] In some embodiments, the chiral system includes chiral metal or semiconductor nanoparticles, such as at least one of gold, silver, palladium, platinum, CdS, or perovskite nanoparticles, or any combination thereof.
[0105] In some embodiments, the electrode is configured as a photoabsorber. Additionally or alternatively, the substrate can be configured as a photoabsorber.
[0106] In some embodiments, the electrode includes at least one layer of a light absorber carried by a substrate.The chiral system can include at least one layer of a light absorber having chiral properties.
[0107] In some embodiments, the electrode includes light absorbing nanoparticles bound to the substrate via a chiral system.
[0108] According to another broad aspect of the present disclosure, there is provided an electrochemical cell system comprising an electrochemical cell and an electrode as defined above, the electrochemical cell being configured to at least one of: electrolyze at least a first electrolyte or convert the chemical energy of a fuel into electricity, wherein the electrode carries a chiral system and is configured to interact with the first electrolyte of the electrochemical system. The interaction between the chiral electrode and the first electrolyte is configured to change the spin state at the electrode-electrolyte interface so as to optimize the operation of the electrochemical system. The optimization of the operation of the electrochemical system can be achieved, for example, by reducing the impedance of the battery and improving the number of charging cycles.
[0109] In some embodiments, the electrochemical cell further comprises a counter electrode that can be connected to the chiral electrode and is configured to interact with a second electrolyte that is chemically connected to the first electrolyte, wherein potential energy can be applied between the chiral electrode and the counter electrode. The counter electrode may include a substrate having a conductive surface that at least partially carries the chiral system. The substrate may be made of at least one of a metal, a chiral conductor, and a semiconductor. The first electrolyte and the second electrolyte may be made of the same or different materials.
[0110] In some embodiments, the electrochemical cell further includes a membrane configured to create a separation between the first electrolyte and the second electrolyte.
[0111] In some embodiments, the film comprises a substrate having a conductive surface at least partially carrying a chiral system as defined above. The substrate may be made of at least one of a metal, a chiral conductor, and a semiconductor.
[0112] There is a need in the art for novel methods of oxygen reduction reaction (ORR) that can reduce the overpotential of the reduction reaction. Overpotential is an electrochemical term that refers to the potential difference between the thermodynamically determined reduction potential of a half-reaction and the potential at which the reaction is observed experimentally, and therefore describes the cell voltage efficiency. Overpotential is a common problem for oxygen reduction systems because the system typically requires a relatively high potential to initiate compared to the working potential, i.e., the equilibrium potential of the net redox reaction.
[0113] The present disclosure provides an electrode to be used in an oxygen reduction system (e.g., a fuel cell system) and a coating for an electrode. Such an electrode is characterized in that, even for an electrode with a large SOC, the efficiency of electron transfer to oxygen (oxygen reduction reaction) is improved and the operation is enhanced. The electrode of the present disclosure is made of a chiral conductor or a conductor coated with a chiral material / structure. The inventors have demonstrated a lower overpotential and a higher current density of a chiral catalyst relative to an achiral catalyst. This effect is caused by the spin selectivity of the electronic current imparted by the chiral assembly, i.e., the chirality-induced spin selectivity effect.
[0114] The present inventors hypothesized that the multi-electron reduction (ORR) of diatomic oxygen is enhanced by the use of spin-polarized electrons and that chiral biomolecules, which are known to polarize electron spins via the chirality-induced spin selectivity (CISS) effect
[55] , can be used to improve ORR efficiency. Previous work has shown that electron transfer through proteins is spin-dependent
[56] , including proteins involved in respiration
[57] .
[0115] The inventors examined the electrochemical ORR at electrodes modified with chiral organic monolayers, testing the effect of chirality on metal films and on platinum nanoparticles and gold nanoparticles. In each case, the inventors compared the ORR performance (particularly the onset potential and current density) of the chirally modified electrodes with the ORR performance of their achiral analogs. Platinum nanoparticles were specifically selected because they are preferred catalysts in fuel cells
[58] . In some embodiments, the electrochemical cell system is configured to be immersed in a solution containing oxygen and is capable of operating to enhance electron transfer from the electrode to oxygen and reduce the overpotential of the oxygen reduction reaction.
[0116] The sharp rise in energy demand and interest in green energy has greatly enhanced the demand for energy storage devices. Lithium-ion batteries (LIBs) are the most common type of electrochemical energy storage and are used in a variety of industries, including electric vehicles, phones, portable electronics, and fixed grid power stations. Among them, nickel-rich layered lithium transition metal oxides (LiNi 1-x-y Co x Mn y Ni (NiO2) has become one of the promising cathode materials for next generation lithium ion battery applications due to its specific capacity and high operating voltage. However, these materials suffer from structural / interface instability, which leads to safety issues in particular. In the present disclosure, the inventors demonstrate that a thin layer coating of polyalanine chiral molecules can protect and improve the performance of Ni-rich cathodes. Specifically, NCM811 electrodes coated with chiral molecules exhibit lower voltage hysteresis and better rate performance. The inventors correlate these results with the chirality-induced spin selectivity (CISS) effect, which enables the resistance of the electrode interface to be reduced by arranging the electron spins and significantly reduces the overpotential required for the chemical process.
[0117] Therefore, according to another broad aspect of the present disclosure, there is provided an energy storage device (e.g., a source of an electric power system), comprising at least one electrochemical cell as defined above, an electrical module for applying a potential difference between an electrode and a counter electrode connectable to the electrode for at least one of charging and discharging the energy storage device, wherein the energy storage device is configured to cause a reduction in the potential difference applied between the electrode and the counter electrode for at least one of charging and discharging the energy storage device due to charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected from or into the surface caused by interaction between the chiral system and the electrode.
[0118] In some embodiments, at least one of the first electrolyte and the second electrolyte includes an active material that is a chiral material.
[0119] In some embodiments, the energy storage device is configured as an electrical battery.
[0120] In some embodiments, the energy storage device is configured as an electrochemical capacitor.
[0121] The technology relates to processes with improved work functions of surfaces covered with chiral molecules, and corresponding uses, especially energy storage devices such as batteries with improved charging time, or other electrochemical processes involving electrochemical cells operated, for example, as electrolyzers (e.g., hydrogen, aluminum dihydrochlorin electrolyzers). Therefore, in some embodiments, the subject matter disclosed herein relates to methods used in batteries and the batteries themselves. When electrons flow from one material to another in a battery cell, the spin of such electrons has an effect on the work function and internal resistance. The reduction of the work function and internal resistance of batteries and battery components is an important aspect in the overall performance of the battery. In particular, reducing the internal resistance of such energy storage devices can lead to more efficient electrochemical reactions, reduce resistivity waste, and improve energy storage device performance (e.g., capacity, charging time, reduced temperature, etc.). The battery can be a rechargeable battery or a disposable battery.
[0122] According to another broad aspect of the present disclosure, there is provided a method of using an electrode as defined above in an electrochemical system. The method comprises interacting between an electrode (i.e., an anode) and an electrolyte of the electrochemical system and transferring a current from the electrode to the electrolyte so as to cause charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected from or to the surface, thereby reducing the work function of the chiral electrode, the interaction between the chiral electrode and the electrolyte being configured to change the spin state at the electrode-electrolyte interface so as to optimize the operation of the electrochemical system.
[0123] According to another broad aspect of the present disclosure, a photovoltaic cell module is provided, the photovoltaic cell module comprising at least one photovoltaic cell, the at least one photovoltaic cell being configured and operable to receive light, convert the energy of the received light into electrical energy and generate electrical power; at least one pair of electrodes, the at least one pair of electrodes electrically coupling the photovoltaic cell and being configured and operable to collect electricity; and a layer having a conductive surface at least partially carrying a chiral system, the layer being placed between the at least one photovoltaic cell and the at least one pair of electrodes and being configured and operable to enhance the performance and efficiency of the photovoltaic cell module. In this regard, it should be noted that under sunlight irradiation, excitons are generated in the active region of a photovoltaic cell (e.g., a Si solar cell). Charge separation between excited electrons and holes is critical to achieving high operating efficiency. This is typically achieved by realizing a P / N junction or a P / I / N junction. Therefore, doping of the active region is critical in all photovoltaic cells, but loss mechanisms are also generated due to non-radiative recombination decay in the active region. These scattering effects reduce cell efficiency. The excited electrons travel to the collector and through an external circuit, generating current. The electron-hole recombination rate is a key factor in photovoltaic cell efficiency. Another loss mechanism is caused by the overpotential barrier that the charge needs to cross before entering the electrode / current collector. The novel technology of the present disclosure can reduce the electrode overpotential at the current collector and improve the charge separation efficiency while reducing recombination losses.
[0124] The conductivity of semiconductors such as silicon is several orders of magnitude lower than that of metals. In order to increase the possibility of electrons reaching the collector and reaching the external circuit through the collector, most batteries utilize metal-based contacts / collectors. Typically, the top contact will have a grid pattern (because it needs to transmit electricity out of the battery while transmitting light into the battery). The bottom contact will usually be a full metal "sheet". The key design trade-off in the top contact design is the balance between the increased resistive losses associated with the wide-pitch grid and the increased shielding caused by the narrow spacing. The interface between the semiconductor cell and the metal contact is another parameter that affects the loss of the compound at the contact resistivity, the current crowding at the edge of the contact (the driving factor of the additional resistivity) and the contact. Reducing the resistance at the metal contact and semiconductor interface can lead to a more efficient photovoltaic cell with less compound loss and resistivity loss, thereby improving overall battery performance. When electrons flow from the semiconductor to the contact, the spin of such electrons affects the resistance at the interface. The arranged spins reduce the resistivity and allow more electrons to be transferred to the external circuit.
[0125] In the present disclosure, the inventors provide a contact and a coating for a photovoltaic cell contact, which coating shows improved electron transfer efficiency. The contact or a component of the contact is made of a chiral system or coated with a chiral system. The chiral system enhances spin selectivity through the CISS effect, and the arranged spin drives a lower resistivity, thereby reducing the electrode overpotential at the collector. In addition, the presence of chiral molecules on both the positive contact and the negative contact reduces the recombination of electrons and hole pairs due to charge separation. If the positive contact and the negative contact are chiral, similar charge separation occurs, thereby improving the charge separation efficiency while reducing recombination losses.
[0126] In some embodiments, at least one electrode of the photovoltaic cell module comprises a substrate having a conductive surface at least partially carrying a chiral system. The chiral system of the photovoltaic cell module may be as defined above. The substrate of the photovoltaic cell module may be made of at least one of a metal, a chiral conductor, and a semiconductor.
[0127] According to another broad aspect of the present disclosure, there is provided an electrical component comprising a substrate having a conductive surface at least partially carrying a chiral system, wherein the chiral system is configured to control the work function of the electrical component, and the interaction between the chiral system and the electrical component causes charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected from or into the surface, so as to reduce the work function of the electrical component and the electrical internal resistance of the electrical component. The chiral system may be as defined above. The substrate of the electrical component may be made of at least one of a metal, a chiral conductor, and a semiconductor.
[0128] In some embodiments, the electrical component is configured as an electrical switch configured to control a flow of electricity of an energy source.
[0129] In some embodiments, the electrical component is configured as an electrical connector configured to electrically couple a plurality of circuits. BRIEF DESCRIPTION OF THE DRAWINGS
[0131] For a better understanding of the subject matter disclosed herein and for the purpose of illustrating how the same may be implemented in practice, embodiments will now be described, by way of non-limiting examples only, with reference to the accompanying drawings, in which:
[0132] Figure 1 is a flow chart illustrating the main steps of a method for controlling the work function of at least one electrode according to the teachings of the subject matter disclosed herein;
[0133] Figure 2is a graph showing the different work functions obtained for different electrodes made of gold, gold coated with a monolayer of L-cysteine, gold coated with a monolayer containing a mixture of the L enantiomer and the D enantiomer of cysteine, and gold coated with a monolayer of 3-mercaptopropionic acid (MPA);
[0134] Figure 3 is a schematic diagram of an electrode and a mechanism affecting the work function of an electrode surface according to the teachings of the subject matter disclosed herein;
[0135] Figure 4A-4B Specific and non-limiting examples illustrating possible uses of electrodes of the subject matter disclosed herein in electrochemical systems are shown, in particular, Figure 4A shows a schematic diagram of a possible electrochemical cell, and Figure 4B The potential barriers over time for different configurations of electrochemical cells are shown;
[0136] Figure 5 A scheme of the manufacturing process for coating the active material of a battery with chiral molecules is shown;
[0137] Figure 6A-Figure 6I The characterization of particles of electrode materials coated with chiral molecules is described, in particular, Figure 6A-6D The S 2p in samples chiral-A, chiral-B, achiral-C and pristine NCM811 are shown. Fig. 6A )、N 1s( Figure 6B )、Co 2p( Figure 6C ) and Ni 2p( Fig.6D )’s XPS spectrum; Fig. 6E The XRD diffraction peaks of the NCM powder sample in the 2θ range of 10°-80° are shown; Figure 6F-Figure 6I A high-resolution SEM image of a powder sample is shown. Figure 6F-6G The high and low magnification images of sample chirality-A are shown, respectively, and Figure 6H-Figure 6I High and low magnification images of the original NCM811 sample are shown respectively;
[0138] Figure 7A-7C Electrochemical measurements of chiral-A, chiral-B, achiral-C and pristine NCM811 / Li half-cells are shown: IV curves ( Fig. 7A )、Discharge capacity rate curve( Figure 7B ) and the cycling stability performance at 1C rate ( Figure 7C ); All measurements were performed at 35°C in 1M LiPF6 EC / EMC (3:7) electrolyte solution;
[0139] Figure 8A-8H Postmortem analysis is shown: Figure 8A-8C Chiral-A and Figure 8D-8F SEM and EDX spectra of the original NCM811 cycled electrode at 1C rate; Figure 8G Comparative XRD patterns of the pre- and post-cycle electrodes of the chiral-A and P-NCM811 samples are shown. Figure 8H A selective XRD pattern of the (003) plane is shown;
[0140] Fig. 9 A schematic layout of an electrochemical setup is shown, which includes a gold working electrode coated with a self-assembled monolayer (SAM) of chiral or achiral molecules;
[0141] Figure 10A-10C The spectra obtained by polarization modulation-infrared reflection-absorption spectroscopy (PM-IRRAS) characterizing the monolayer formed on the gold electrode are shown, in particular, Fig. 10A Spectra of Au surfaces coated with 3-mercaptopropionic acid (achiral) and L-cysteine (chiral) are shown; Fig. 10B shows spectra of various achiral alkanethiols used in the experiments; and Fig. 10C Spectra of various chiral oligopeptides used in the experiments are shown;
[0142] Figure 11A-11C The oxygen reduction activity of the molecularly coated electrodes is shown, in particular, Fig.11A Shown are the currents versus potential measured in 0.1 M KOH solutions saturated with N2 (dashed lines) and O2 (solid lines) when the electrode is coated with a monolayer of an achiral molecule (achiral 3-mercaptopropionic acid, blue curve) or a chiral molecule (L-cysteine, red curve); Figure 11B-Figure 11C The results show that the electrode is coated with an achiral molecule (1-octadecanethiol) ( Fig. 11B ) and chiral oligopeptide (L-ala5)( Fig. 11C ) monolayer measured with respect to the potential;
[0143] Fig.12 The current versus potential of three electrodes, namely, commercial Pt / C electrode, achiral Pt NP electrode, and chiral Pt NP electrode, are shown;
[0144] Figures 13A-13D shows the molecular length dependence of oxygen reduction, in particular, Fig.13A and Fig. 13B Various lengths of achiral molecules are shown ( Fig.13A ) and chiral molecules ( Fig. 13B )'s current versus potential curve for a monolayer; Fig. 13C and Fig.13D The achiral ( Fig. 13C ) monolayer and chirality ( Fig.13D ) The onset potential of the monolayer-modified working electrode relative to the molecular length;
[0145] Figures 14A-14D The resistance characterization of chemically coated electrodes is described; in particular, for electrodes coated with achiral ( Fig.14A ) single layer or chiral ( Fig. 14C ) Cyclic voltammetry curves obtained for the single-layer electrode; Fig. 14B and Fig.14D The results for achiral molecules ( Fig. 14B ) and chiral molecules ( Fig.14D ) presents the peak current density of long and short molecules;
[0146] Fig.15A and Fig. 15B It is shown that in a three-electrode system ( Fig.15A ) achiral molecules (1-decanethiol, 1-octadecanethiol) and ( Fig. 15B ) Electrochemical impedance spectroscopy of surfaces coated with chiral molecules (L-ala3, L-ala7); Fig. 15C An equivalent circuit model for fitting the electrochemical impedance spectrum is shown; Fig.15D is R estimated from the equivalent circuit model s Value and R ct Summary of values;
[0147] Fig.16A and Fig. 16B The circular dichroism spectra of the synthesized gold (Au) films with L-tartaric acid or DL-tartaric acid are shown in Fig.16A ) and UV-visible absorption spectra ( Fig. 16B ); Fig. 16C The ORR performance of the synthesized Au thin film is shown;
[0148] Fig.17A and Fig. 17B The circular dichroism spectra of synthesized gold nanoparticles (AuNPs) with L-cysteine or DL-cysteine are shown in Figure 2. Fig.17A ) and UV-visible absorption spectra ( Fig. 17B ); Fig. 17C Shown are the currents measured with gold nanoparticles (Au NPs) of different chirality versus potential;
[0149] Figures 18A-18D Characterization of the morphology of Pt nanoparticles (NPs) is shown, in particular, Fig.18A and Fig.18C Transmission electron microscopy (TEM) images are shown, and Fig.18B and Fig.18D The results show that the use of L-cysteine ( Fig.18A , Fig.18B ) or DL-cysteine ( Fig.18C , Fig.18D ) Size distribution of modified Pt NPs;
[0150] Fig.19A and Fig.19B The circular dichroism spectra of synthesized Pt nanoparticles (PtNPs) with L-cysteine or DL-cysteine are shown in Figure 2. Fig.19A ) and UV-visible absorption spectra ( Fig.19B ); Fig.19C The ORR performance of Pt NPs is shown; Figure 19D-19F The electrochemical properties of Pt catalysts are shown, where chiral Pt NPs ( Fig.19D ) and achiral Pt NPs ( Fig.19E ) and commercial Pt / C catalysts ( Fig.19F )’s cyclic voltammetry (CV) curve, Figure 19G Shown are the currents versus potentials measured with platinum nanoparticles (Pt NPs) of different chirality, with a commercial Pt / C catalyst added for comparison;
[0151] Figures 20A-20F The effect of chiral molecules is shown, in particular, Fig. 20A The dependence of spin polarization on the length of the chiral oligopeptide is shown; Fig. 20B Calculations of the number of electrons transferred are shown, specifically, the current versus potential measured with a monolayer of L-ala3 and L-ala7 in an O2-saturated 0.1 M KOH electrolyte at a scan rate of 50 mV / s; Fig. 20C shows the splitting of the spin states of triplet oxygen upon interaction with spin-polarized electrons residing on a chiral molecule; Fig.20D and Fig.20E It is shown that in the chiral system ( Fig.20D ) and in the case of achiral systems ( Fig.20E ) possible spin states in the case of Fig.20F shows the calculated triplet energy level on oxygen presented as a function of the distance between the chiral molecule and oxygen;
[0152] Fig.21 Possible configurations of energy storage devices including electrochemical cells configured as batteries are shown, wherein each of the battery electrodes includes a respective substrate having a conductive surface and carrying a respective chiral system according to the principles of the present disclosure;
[0153] Fig. 22A possible configuration of a photovoltaic cell module comprising a photovoltaic cell is shown, in particular each of the electrodes of the photovoltaic cell comprising a respective layer having a conductive surface at least partially carrying a chiral system according to the principles of the present disclosure;
[0154] Fig.23A and Fig. 23B A possible configuration of an electrical component comprising a substrate having a conductive surface at least partially carrying a chiral system is shown, in particular, Fig.23A A junction field effect transistor (JFET) is shown in which a chiral coating covers electrodes of gate, source and drain terminals; and Fig. 23B An interconnect comprising a metal layer, a magnetic layer or a superconductor layer and two contacts / electrodes is shown, wherein a chiral coating lines the interface between the outer surface of the metal layer, the magnetic layer or the superconductor layer and the contacts / electrodes;
[0155] Fig.24A and Fig. 24B A possible configuration of an energy storage device configured as an electrochemical capacitor is shown, in particular, Fig.24A An electrochemical capacitor comprising two electrodes separated by an ion-permeable membrane (diaphragm), each of the electrodes being coated with a chiral system according to the principles of the present disclosure; and Fig. 24B An electrochemical capacitor comprising two charged conductive plates, one plate being positively charged and one plate being negatively charged, wherein a dielectric layer separates the conductive plates; each of the conductive plates being coated with a chiral system according to the principles of the present disclosure; and
[0156] Fig.25A and Fig.25B Two possible configurations of an electrochemical cell system are shown, in particular, Fig.25A An electrochemical cell configured as a water electrolyzer is shown, the electrochemical cell comprising two electrodes, an anode and a cathode, both of which carry a chiral system according to the principles of the present disclosure; and Fig.25B An electrochemical cell configured as a fuel cell is shown, with both electrodes of the cell, the anode and the cathode, carrying a chiral system as described in the present disclosure.
[0157] Detailed description of implementation plan
[0158] refer to Figure 1, a method 100 for controlling the work function Wf of at least one surface is shown. The method 100 includes measuring a first work function Wf1 of a first surface in 102, depositing a chiral system on the first surface to cause a change in the first work function Wf1 in 104, and applying a potential difference between the first surface and the second surface in 106 so that a charge is transferred between the first surface and the second surface. The interaction between the chiral system and the first surface is configured to cause charge rearrangement, spin polarization of the first surface, and spin polarization of electrons injected from or into the first surface, thereby changing the work function Wf1 of the first surface. Depositing the chiral system on the first surface in 104 may include chemically binding the chiral system to the first surface in 104A, such as in the case of binding thiol to gold, or physically adsorbing the chiral system on the first surface in 104B, such as in the case of depositing a chiral oxide.
[0159] If the technology of the present disclosure is implemented to improve an electrochemical process (wherein the first surface and the second surface are used as the first electrode and the second electrode, and the transfer of electric current between the two electrodes involves an electrochemical reaction and electron transfer between two species), the method 100 may also include immersing the first surface and the second surface in an electrolyte before applying the potential difference at 108. Since electrical energy is directly converted into chemical energy during the electrolysis process, the interaction between the chiral first surface (used as an electrode) and the electrolyte is configured to change the spin state at the electrode-electrolyte interface and reduce the applied potential difference, which should have been applied regardless of whether the chiral system is deposited on the electrode surface, as described below with respect to Figure 4B As will be further illustrated. Therefore, when measuring the second work function of the first surface carrying the chiral system in 110, a change in the work function of the first surface is observed such that Wf2<Wf1, ie, the second work function is lower than the first work function.
[0160] refer to Figure 2, shows the difference in work function between a reference electrode and a gold (Au) surface measured by a Kelvin probe, the gold (Au) surface being bare or coated with a monolayer of a chiral molecule (e.g., cysteine) or a monolayer coated with a mixture of the L enantiomer and the D enantiomer of cysteine, or a monolayer of the achiral molecule 3-mercaptopropionic acid (MPA). More specifically, the work function of the bare gold surface is -565 mV, the work function of the gold surface coated with a monolayer of L-cysteine is -305 mV, the work function of the gold surface coated with a monolayer of a mixture of the L enantiomer and the D enantiomer of cysteine is -412 mV, and the work function of the gold surface coated with the achiral molecule is -393 mV. In this regard, it should be noted that an achiral monolayer can change the work function of the electrode surface, but it increases the resistance of the electrode and is therefore less relevant for electrochemical applications. In the case of chiral molecules, the resistance of the chiral film is low due to the CISS effect, and the reduction in work function compensates for the slight increase in resistivity. Therefore, it has been clearly shown that the presence of chiral molecules significantly reduces the work function of the electrode surface. The work function of gold coated with a chiral monolayer is the minimum work function (-305mV).
[0161] The inventors have found that when a chiral material comes into contact with an electrode surface, a charge rearrangement occurs in the chiral material. This charge rearrangement is accompanied by spin polarization. Therefore, the binding of the molecule to the substrate requires that the electrons of the substrate have a spin opposite to the spin of the chiral material. The additional energy generated by the charge rearrangement is proportional to the degree of spin polarization multiplied by the spin exchange interaction, and is further proportional to the common chemical energy associated with the binding, thereby stabilizing the binding.
[0162] refer to Figure 3 , an example of an electrode 300 for an electrochemical process of the present disclosure is shown. When a chiral system 304 is carried by a substrate 302 having a conductive surface, the chiral system 304 is charged and spin-polarized. The substrate 302 can be made of metals and / or semiconductors such as Pt, gold, silicon, or Cu. In order to bind to the surface, the spins of the electrons on the surface 302 must be arranged in the opposite direction to the spins of the electrons belonging to the molecule and close to the substrate. Therefore, the chiral layer 304 induces spin polarization in the outermost atoms. Therefore, the electrons injected from the surface 302 or the electrons injected into the surface 302 are spin-polarized so that they are smoothly transferred through the interface and the chiral molecules 304. In this way, the chiral system 304 is configured to control the work function Wf of the electrode surface 302, so that the interaction between the chiral system 304 and the substrate 302 causes charge rearrangement, spin polarization of the surface 302, and spin polarization of the electrons injected from the surface 302 or the electrons injected into the surface 302. The stabilization energy due to binding is the fraction of electrons that are spin polarized times the spin exchange energy.
[0163] refer to Figure 4A , shows an example of an electrochemical cell 400 using electrodes of the subject matter disclosed herein. The electrochemical cell 400 includes an electrode 402, which is made of a Zn substrate coated with a chiral molecule and immersed in an aqueous ZnSO4 electrolyte. The electrochemical cell 400 also includes a counter electrode 404 connected to the chiral electrode 402 via an electrical module 406, which is configured to apply an electrical potential energy between the electrode 402 and the electrode 404. The counter electrode 404 is made of Cu and is configured to be immersed in an aqueous CuSO4 electrolyte. The aqueous ZnSO4 electrolyte and the aqueous CuSO4 electrolyte are separated by a permeable (e.g., porous) membrane that prevents them from mixing rapidly but allows ions to diffuse through. The membrane can be a conventional membrane or can include a substrate having a conductive surface that at least partially supports the chiral system. When the Zn 2+ The excess electrons remaining when the ions emerge from the Zn substrate in the left cell will be able to flow through the external circuit and into the right electrode, where they can be transferred to the Cu 2+ Ion, Cu 2+ The ions are "discharged", i.e. converted into Cu atoms at the surface of the copper electrode. The net reaction is the oxidation of zinc by copper(II) ions: the reaction can be started and stopped by connecting or disconnecting the two electrodes. By connecting a battery or other current source to the two electrodes, we can force the reaction to proceed in its non-spontaneous or opposite direction. The chiral molecule can be deposited on the zinc electrode 402 as in this example, but can alternatively be deposited on the copper electrode 404, or on both. The presence of the chiral molecule on the Zn substrate enables the applied voltage to be reduced to force the reaction to occur and generate a current.
[0164] If the electrochemical cell 400 is used as a source of an electric power system (e.g., a Zn-Cu battery) in which the current is generated from a spontaneous oxidation-reduction reaction, a substantial reduction in the potential barrier can be measured when the zinc electrode 402 (i.e., the cathode) is covered with a chiral coating, thereby significantly improving the charging time. Typically, the source of an electric power system includes a plurality of electrochemical cells interconnected (in series and / or in parallel) therebetween.
[0165] Figure 4BIt is a graph showing the potential of different configurations of an electrochemical cell over time, indicating the charging time and potential barrier of batteries with different configurations. The first curve 408A shows the potential measured when the anode and cathode are coated with alpha-helical chiral molecules. In this regard, it should be noted that in some cases, coating two electrodes may be beneficial to reduce the potential barrier, and in other cases, such as in this specific and non-limiting example, depending on the specific relative potential of the two electrodes, coating two electrodes may not reduce the potential barrier. The second curve 408B shows the potential measured when only the anode is coated with a chiral molecule. The third curve 408C shows the potential measured when only the cathode is coated with a chiral molecule, and the fourth curve 408D shows a control measurement without molecular aggregates. It is clearly shown in the figure that, compared with an electrochemical cell in which the anode and cathode are not coated, coating the cathode with a chiral coating produces a substantial reduction in the potential barrier for starting the electrochemical process, which is indicated by the increase in the potential obtained in the electrochemical cell in which the cathode is coated with a chiral molecule (from about 1.090V to about 1.094V).
[0166] In the following, the enhancement of cathode performance of lithium-ion batteries by chiral molecular coatings is described in detail.
[0167] To investigate the effect of CISS on Li-ion batteries, the inventors adsorbed chiral AHPA molecules onto the active materials of the battery. The term "active material" hereinafter refers to the material responsible for the reversible electrochemical reactions that occur during the charge and discharge cycles. The active material may be present in the positive and negative electrodes, or in the electrolyte. The active material may be an intrinsically chiral material, or a material coated with a chiral material. The electrolyte may be solid or liquid, and may or may not have chiral properties. The flow process of coating the cathode material with chiral molecules is described in detail in the literature. Figure 5 Commercial LiNi purchased from TARGRAY-USA 0.8 Co 0.1 Mn 0.1The cathode powder of O2 (NCM811) is UV treated before inserting the L-α-helix-polyalanine (AHPA) of 3008.71g / mol 1mM ethanol solution. 4g of NCM811 powder is coated with APHA with a total amount of 3mg. The reactor is gently shaken during the coating process to homogenize the suspension. After drying the sample for 24 hours under a nitrogen environment, the coated NCM811 powder (chirality-A) is obtained. In the chiral-B sample, for the coated NCM811, the same concentration of 1mM is used, but the sample is not dried in the solution, but washed by a chiral solution using 2μm filter paper (chirality-B). The control sample is prepared in the same manner as the chiral-A process, but an achiral molecule (12-mercaptododecanoic acid SigmaAldrich, 232.38g / mol) (achiral-C) is used. The proposed procedure is extremely simple and can be easily scaled up for battery production.
[0168] The crystal structure of the samples was determined using X-ray diffraction (XRD, D8 advance, Bruker). The chemical composition of the coating with the cathode material was analyzed by X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-α) under Al Kα radiation. -10 X-ray photoelectron spectroscopy (XPS) measurements were performed using a 5600 Multi-Technique System (PHI, USA) at a torr base pressure. The samples were irradiated with an Al Kα monochromatic source (1486.6 eV) and the escaped electrons were analyzed by a spherical capacitor analyzer using a slit aperture of 0.8 mm. The morphology of the samples was analyzed using a high-resolution scanning electron microscope (HRSEM) FEI, Magellan 400Lis. The morphology and microstructure of the samples were detected by field emission scanning electron microscopy (Nova Nano SEM 450, FEI) and high-resolution transmission electron microscopy (HRTEM, Tecnai G2 F20, FEI).
[0169] FIG. 6A to FIG. 6D Shown are the XPS spectra of samples Chiral-A, Chiral-B, Achiral-C and pristine NCM 81 1. The results suggest that the organic material is adsorbed on the NCM particles. Fig. 6A The presence of organic material indicated by the 2S peak in the treated samples is shown. Figure 6B A typical XPS spectrum of N 1s is presented, where a peak at 400.1 eV is observed that is associated with pyrrolic N and can be related to the amino group in the chiral peptide. Figure 6C), in addition to the two satellite peaks at 879.6 eV and 861.5 eV, the other two peaks at 873.5 eV and 855.9 eV are attributed to Ni 2p 1 / 2 and Ni2p 3 / 2 .also, Fig.6D Shows the Co 2p 1 / 2 and Co 2p 3 / 2 The two significant peaks at 796.6 eV and 780.9 eV indicate the presence of Co in all samples of chiral-A, chiral-B, achiral-C and pristine NCM811. 2+ and Co 3+
[59] . Given the nominal calculated length of AHPA of 5.4 nm and achiral of 2.6 nm, the Ni and Co transition metals (TM) in the uncoated NCM particles were three times higher compared to the coated samples, as expected due to the coating
[60] . By comparing the binding energy values of the original NCM811 cathode and the chiral coated NCM811 cathode, no shift was obtained (Table 2 below). XPS analysis indicated that the chiral coating on the NCM811 cathode did not change the interfacial composition or oxidation state of the NCM811 core.
[0170] Fig. 6EThe XRD diffraction peaks of the NCM powder samples in the 2θ range of 10°-80° are shown. All diffraction peaks are well indicated by the corresponding crystal planes of the hexagonal crystal structure with space group R-3m. As can be seen from the diffraction, the adsorption of chiral molecules does not change the properties of NCM, and the non-chiral molecules do not change the properties of NCM either. XRD patterns of the prepared powders, from which highly crystalline layered structures of all four samples can be observed. All diffraction peaks point to the hexagonal α-NaFeO2 structure with space group, and there is no obvious change in the XRD patterns of the coated samples and the original NCM, which indicates the similar crystal structure of the cathode material before and after surface modification. The results also indicate that there are no impurities in the NCM powder samples, indicating that due to the nature of the thin coating (which is not detected by XRD), the chiral molecules: L-α helical polyalanine (AHPA) and non-chiral molecules: 12-mercaptododecanoic acid (MDA) on the surface of the NCM particles are small and amorphous
[61] . Typically, the intensity ratio of the (003) and (104) diffraction peaks can be used to determine the order of cations in NCM materials, and the ratio value is inversely proportional to the cation order. When the ratio> 1.2, the layered structure with a lower degree of cation mixing is more stable. After calculation, the I(003) / I(104) ratios of the four samples chiral-A, chiral-B, achiral-C and original NCM811 were 1.35, 1.46, 1.35 and 1.58, respectively. In addition, the split doublets of (006) / (102) and (108) / (110) indicate the order of the material crystal structure that is not affected by the chiral protected cathode material. The two results well confirm that the material has a layered structure. In summary, it is concluded that after the chiral protective coating on the original NCM811, the NCM sample with a layered structure can be successfully retained.
[0171] Electron microscopy (HRSEM) images of chiral-A and pristine NCM811 FIG. 6F to FIG. 6I Presented in. Figure 6F-6G The high and low magnification images of sample chirality-A are shown, respectively, and Figure 6H-Figure 6I High and low magnification images of the sample original NCM811 are shown respectively; HRSEM images show that the chiral coating and non-chiral coating on the NCM811 particles are not affected or degraded by the adsorption process, and the spherical structure of the particles is retained. The element map of the individual particles shows that the coating is uniform around the particle surface. The results are summarized in Table 1 below.
[0172]
[0173] Table 1
[0174] Electrochemical tests were performed using a 2032 coin-type test cell. A cathode comprising a polyvinylidene fluoride (PVDF) binder (10 wt%), acetylene black (10 wt%) and a chirally coated NCM811 active material (80 wt%) was dispersed into N-methylpyrrolidone (NMP) to prepare a uniform slurry. The slurry was cast onto an aluminum foil and dried on a hot plate, followed by drying overnight at 110 ° C under vacuum to evaporate the NMP solvent. The dried cathode was cut into a circular shape with a diameter of 12 mm as the cathode electrode of the LIB coin cell, and the mass loading of the active material was ≈2.34 mg. Lithium foil (200 μm thick) and Celgard PP2500 polypropylene film were used as anode and separator, respectively. A commercial electrolyte solution LP-57 containing 1M LiPF6 in an ethylene carbonate-ethyl methyl carbonate mixture (3: 7; v: v) was used as an electrolyte. The assembly of coin cells (CR-2032) was carried out in an argon-filled glove box, and the moisture and oxygen contents were ≤0.1 ppm. Cycling and rate performance were performed galvanostatically at room temperature (30 °C) using a Neware battery tester in the voltage windows of 2.8 V-4.3 V and 2.8 V-4.5 V (vs. Li / Li+), respectively. The rate performance was performed on a Biologic (VSP) system at 0.1 mV s -1 Cyclic voltammetry (CV) was performed at a potential scan rate of 0.01 Hz-10 and a perturbation amplitude of 5 mV. 5 Electrochemical impedance spectroscopy (EIS) tests in the frequency range of Hz.
[0175] IV curves of uncoated NCM811 (original) and coated NCM811 electrodes (relative to Li counter electrode) Fig. 7A Both the uncoated NCM811 sample and the coated NCM811 sample exhibit two voltage plateaus at ˜3.7V and ˜4.2V. Fig. 7A The overlaid voltage curves in show two main observations. First, a lower average overpotential is obtained by chiral coated NCM811 relative to achiral coated NCM811 or uncoated NCM811. Second, cells with chiral coated NCM exhibit higher specific discharge capacity than achiral coated NCM or uncoated NCM.
[0176] The performance of the samples was evaluated using coin-type CR2032 lithium half-cells at voltages ranging from 2.8 V to 4.3 V at rates ranging from 0.1C (discharged at 10 hours) to 4C (discharged at 15 minutes). The initial charge-discharge curves for all four samples at 0.1C rate were formed at Fig. 7A. The specific discharge capacities of chiral-A, chiral-B, achiral-C and pristine NCM cathodes are 217.7+-1 mAh / g, 209 mAh / g, 207 mAh / g, 206 mAh / g, respectively. As can be seen, the rate performance is improved by the surface coating. At low C-rates (0.1C and 0.2C), chiral-A sample NCM811 provides a larger specific discharge capacity (5 mAh / g-10 mAh / g) than other samples.
[0177] At higher rates of 1C, 2C and 4C, a more significant enhancement of discharge capacity was observed. Compared with the original sample, the specific discharge capacity of the chiral-A sample shows an average increase of 8.7% in the specific discharge capacity at 4C and an average of 6% +-0.2. Samples chiral-B and non-chiral-C show a smaller increase of 5.7% and 4.6% in the specific discharge capacity at 4C and an average of 3% and 1.8%, respectively. These results show that coating NCM811 generally improves the kinetics of the Li insertion / deintercalation process because both the chiral coating and the non-chiral coating improve performance. This means that the organic coating can prevent the electrolyte solution from decomposing on the NCM surface, forming a thick passivation layer, which slows down the Li insertion / deintercalation kinetics. However, the battery with a chiral coating is superior to the battery with a non-chiral coating. This shows that, in addition to physical protection, the chiral coating improves the discharge / charge process.
[0178] Overall, the electrochemical performance of all three protected NCM cathode materials chiral-A, chiral-B and non-chiral-C shows better rate performance than the original NCM811. The chiral coating improvement during charge-discharge process leads to a stable configuration and lower resistivity in the battery. The lower the resistivity in the coin cell, the lower the implied voltage for a given discharge rate, which allows us to reach a more stable voltage discharge state. Compared with the original NCM811 cathode, the electrochemical performance in terms of discharge specific capacity is enhanced in all three molecularly protected NCM811 cathode samples chiral-A, chiral-B and non-chiral-C. During the cycle, all samples (coated and uncoated) experience reasonable capacity decay. After 100 cycles at 1C rate, the discharge capacity retention rates of samples chiral-A, chiral-B and non-chiral-C are 84.5%, 89% and 92%, respectively. The uncoated sample of the original NCM811 reaches a discharge capacity retention rate of 91%. Long-term stability of the NCM811 interface using either chiral or achiral coatings was not observed. These results indicate that the protective coating inhibits direct contact between the electrolyte and the NCM811 particles, which stabilizes the electrochemical reactions of the interface and the SEI interfacial layer. The thickness of the coating has a large impact on the electrochemical performance of the cathode material. Thin coatings (1nm-3nm) are not sufficient to protect NCM811, and their ability to hinder side reactions at the interface is poor, as observed here for the chiral-B sample and the achiral-C sample. Thicker coatings (about 10nm) increase stability and performance, as shown for the chiral-A sample, which causes Li + The diffusion path through the chiral molecular protective layer is longer and hinders Li + transfer.
[0179] Finally, after cycling the electrodes, the morphology and composition of the cathode materials were further investigated by using high-resolution scanning electron microscopy (HR-SEM) and EDX spectroscopy. FIG. 8A to FIG. 8F The treated sample Chiral-A electrode showed no cracks and structural degradation on the core NCM 811 particles after continuous electrochemical charge-discharge cycles. In the case of the pristine sample, a clear degradation of the primary particles from the secondary macro-sized particles was observed with almost no crack formation and erosion. Sample Chiral-A ( Figure 8C ) and the original NCM811( Figure 8F ) EDX spectra of the cathode confirm the retention of the NCM811 composition after continuous charge-discharge cycles of the cathode. Thus, the inventors found that the decay was similar in all cases, taking into account longer cycles at higher capacities. Figure 8G and Figure 8H The X-ray diffraction patterns of the chiral protective coated Chiral-A and pristine NCM811 electrodes shown in Figure 4 show the absence of structural and phase changes after continuous cycling.
[0180] Therefore, the inventors have demonstrated that the use of chiral coating technology to modify the surface of NCM811 materials can significantly improve the electrochemical performance of lithium-ion batteries. NCM811 electrodes coated with chiral molecules exhibit lower voltage hysteresis and better rate performance, with a 9% capacity improvement at a 4C discharge rate and an average improvement of 6% in rate performance measurements. On the other hand, the achiral sample showed only a 4.6% capacity improvement and an average improvement of 2% at 4C. These results indicate that the chirality-induced spin selectivity (CISS) effect plays a vital role in the charge / discharge process. Compared with the 92% capacity retention of the achiral treated battery and the 91% capacity retention of the original battery, the capacity retention of the chiral treated battery was only 85% after 100 cycles.
[0181] refer to Fig. 9 , shows a schematic layout of an electrochemical setup comprising a gold working electrode coated with a self-assembled monolayer (SAM) of a chiral molecule or an achiral molecule. The inventors used an electrochemical assay in which O2 was bubbled into an electrochemical cell and the reduction current was monitored. The electrochemical cell was assembled with a Pt counter electrode, an Ag / AgCl reference electrode, and a working electrode that could be chiral or achiral. In the first stage of the work, the inventors utilized a 100 nm thick gold film coated with chiral cysteine and the oligopeptide SH-(CH2)2-NH-(Ala-Aib) n -COOH (n = 3, 5, 7, 8, 11, respectively referred to as L-ala3, L-ala5, L-ala7, L-ala8 and L-ala11) self-assembled monolayers (SAMs) or coated with achiral molecules 3-mercaptopropionic acid and SH-(CH2) n - monolayer of CH3 (n=3, 7, 9, 13, 17) as shown in Table 2 below.
[0182]
[0183] Table 2
[0184] The solution used to prepare the monolayer was first bubbled with Ar for more than 30 min. Non-chiral alkanethiol molecules were dissolved in ethanol to form a 1 mM solution. Chiral oligopeptides were dissolved in 2,2,2-trifluoroethanol (≥99%, Sigma-Aldrich) to form a 1 mM transparent solution. Au film electrodes were prepared on single crystal silicon wafers with a combination of Cr (10 nm) / Au (100 nm) layers by electron beam evaporation. Before adsorption, the surface was cleaned by boiling in acetone and in ethanol for 10 min, followed by UV / ozone treatment for 15 min, and then immersed in ethanol for 40 min. The surfaces were then dried under a nitrogen stream and immediately immersed in a thiol molecule solution for 72 h.
[0185] The monolayer formation was characterized by infrared spectroscopy using polarization modulation-infrared reflection-absorption spectroscopy (PM-IRRAS), and the corresponding spectra were obtained in Figure 10A-10C Spectra were recorded using a Nicolet 6700 FTIR instrument (Hinds Instruments, Hillsboro, OR) equipped with a PEM-90 photoelastic modulator. Each spectrum was obtained by accumulating 2000 scans with the sample mounted at a Brewster angle of 80°. The spectra of 3-mercaptopropionic acid (MPA) and L-cysteine monolayers ( Fig. 10A ) is shown at 3236cm -1 A characteristic peak at 2927 cm-1 belonging to the -CH2 group was also observed. -1 The carboxyl group has a strong peak at 1726 cm -1 There is also a signature of a carbonyl (C=O) stretching mode at 1569 cm -1 This weak vibration band at , which is attributed to the NH bending in the NH2 group. In contrast, the inventors did not observe this peak for the 3-mercaptopropionic acid monolayer ( Fig. 10A ), which is consistent with their molecular structures (Table 1 above). In addition to the NH vibration of the NH2 group, the intensities of the other peaks of both L-cysteine and MPA are almost the same, indicating similar coverage of these surfaces.
[0186] For the alkanethiol-coated Au surface, the -1 Up to 2965cm -1 The strong peaks in the range are attributed to the asymmetric and symmetric CH stretching frequencies of the -CH2 groups present in the alkyl chain ( Fig. 10B ). In addition, from 1-butanethiol to 1-octadecanethiol, the peak intensity increases with the increase of the alkyl chain length.
[0187] Fig. 10CThe PM-IRRAS spectrum of the oligopeptide monolayer is shown. -1 The strong peak at 1542 cm is the typical stretching mode of CO bond (amide-I), while the peak at 1542 cm -1 The peaks at can be attributed to the NH in-plane bending mode and the CN stretching mode (amide-II). In addition, the intensities of these two characteristic peaks increase with the length of the oligopeptide, indicating that the Au surface is successfully coated with different chiral molecules.
[0188] Electrochemical measurements were performed using a three-electrode electrochemical cell equipped with an Ag / AgCl reference electrode and a platinum wire as a counter electrode. The working electrode was an Au film modified with different molecules (see above). Electrochemical data were recorded on a potentiostat (PalmSens4) electrochemical workstation at room temperature. Potentials were measured relative to an Ag / AgCl (3M NaCl) reference electrode, and then calibrated with reference to a standard reversible hydrogen electrode (RHE). The working electrode was static during all measurements.
[0189] Electrochemical reduction was performed with 0.1 M KOH in aqueous solution at pH = 13. Oxygen was bubbled for at least 30 min before starting the measurement to ensure saturation. All applied potentials were converted to a standard reversible hydrogen electrode (RHE) reference scale.
[0190] Under the alkaline conditions studied in these studies, two reduction pathways are generally considered possible
[62] :
[0191] O2+2H2O+4e-→4OH - (1)
[0192]
[0193] Figure 11A-11C The oxygen reduction activity of the molecule-coated electrodes is shown. Fig.11A Presented are current versus voltage plots for electrodes coated with achiral 3-mercaptopropionic acid SAM (blue) or chiral L-cysteine (red) in N2 (dashed line) and O2 (solid line) saturated 0.1 M KOH solutions. The onset potential is defined as the voltage at which the current reaches 0.1 mA / cm 2 The current density is normalized with reference to the geometric area of the working electrode. Fig. 11B and Fig. 11C The results show that the electrode is coated with an achiral molecule (1-octadecanethiol) ( Fig. 11B ) and chiral oligopeptide (L-ala5)( Fig. 11C ) is the current measured relative to the voltage when a single layer is formed.
[0194] The significant difference in current density in O2- and N2-saturated solutions indicates that both the chiral-functionalized electrode and the achiral-functionalized electrode show oxygen reduction activity. Although the two molecules have the same length and very similar structures ( Fig.11A ), but a shift of about 0.25 V in the onset potential of the reduction is clearly evident. It should be noted that more positive potentials mean a lower barrier for ORR, and that the coverage of organic molecules on the Au surface results in an onset potential that is smaller than that found for bare Au, cf. Fig.12
[63] .
[0195] Fig.12 The current versus potential of three electrodes, namely a commercial Pt / C electrode, an achiral Pt NP electrode, and a chiral Pt NP electrode, is shown. The current versus potential was measured with bare commercial Pt / C, achiral Pt NPs, and chiral Pt NPs at a scan rate of 50 mV / s. It is clearly shown in the figure that coating the electrode with a chiral coating produces a reduction in the potential barrier for starting the electrochemical process, which is indicated by an increase in potential. Therefore, the electrodes prepared by using the teachings of the novel technology of the present disclosure are able to reduce the overpotential of the electrode and enhance the charge separation efficiency while reducing recombination losses.
[0196] Fig.13A and Fig. 13B shows that when the electrode is coated with achiral molecules of different lengths ( Fig.13A ) and chiral molecules ( Fig. 13B ), the ORR current versus voltage curve. Fig. 13C As can be seen in Figure 2, the onset potential of the achiral molecule decreases with increasing molecular length, indicating that the reaction barrier increases with increasing SAM thickness. In sharp contrast, the onset potential of the chiral molecule increases with increasing molecular length ( Fig.13D ), indicating that the reaction barrier decreases with increasing SAM thickness. The higher barrier observed for achiral molecules is consistent with the increase in the resistance of the molecule with increasing length and the decrease in O2 solubility with increasing alkane molecule length. The inventors examined whether a lower potential (higher overpotential) is required for thick films to achieve the same current density as observed for thin films. However, surprisingly, for SAMs containing chiral molecules, the potential increases with length, even though it is known that the molecular resistance increases with length, and the diffusion of O2 through the layer to the electrode is expected to decrease with molecular length. The abnormal reduction in the ORR reaction barrier with increasing oligopeptide length is related to the improved spin filtering of oligopeptides with increasing length (see below).
[0197] To confirm that the different behavior was not caused by a significant length difference or SAM mass between the two types of molecules, the ion exchange rate of iron / ferrocyanide (Fe(CN)6 3- / 4- , 10 mM) redox couple, rather than oxygen, and therefore the redox couple in solution is insensitive to chiral or achiral molecules. 3- / 4- Cyclic voltammetry ( Figures 14A-14D ) and electrochemical impedance spectroscopy ( Figures 15A-15D ). The electrochemical impedance spectroscopy was performed in the frequency range of 50 kHz-5 Hz.
[0198] Figures 14A-14D The resistance characterization of chemically coated electrodes is described. Fig.14A ) single layer or chiral ( Fig. 14C ) monolayer electrode. It shows that the short molecule (1-decyl mercaptan ( Fig.14A ) and L-ala3( Fig. 14C )) and long molecules (1-octadecanethiol ( Fig.14A ) and L-ala7( Fig. 14C )) curve; the inset shows the curve for a long molecule, where the current axis is magnified. Fig.14A and Fig. 14C (center) indicates the voltage at which the peak current density is obtained. Fig. 14B and Fig.14D In the figure shown in , non-chiral molecules ( Fig. 14B ) and chiral molecules ( Fig.14D ) for long and short molecules. It should be noted that the ratio between the peak currents is very similar for both types of molecules.
[0199] Since achiral ferrocyanide is a low spin 5 The complex and ferrocyanide are low spin d 6 coordination complex, it is expected that there will be no effect from spin polarization on the electron exchange with the redox pair. In this case, the coating with shorter molecules ( Fig.14A 1-Decanethiol and Fig. 14C The surface of L-ala3 in the Fig.14A Octadecanethiol and Fig. 14C The redox peak current of L-ara7 in α-arabinocyclic adenosine (Ara7) is much higher than that of L-ara7 in α-arabinocyclic adenosine (Ara7), which is independent of whether the molecule is chiral or achiral.
[0200] These findings were confirmed by impedance measurements, which showed that the impedance of both types of molecules increased with length, as shown in Tables 3 and FIG. 15A to FIG. 15D As shown in .
[0201]
[0202] Table 3
[0203] Fig.15A and Fig. 15B It is shown that in a three-electrode system ( Fig.15A ) achiral molecules (1-decanethiol, 1-octadecanethiol) and ( Fig. 15B )Electrochemical impedance spectroscopy of surfaces coated with chiral molecules (L-ala3, L-ala7). Fig. 15C The equivalent circuit model used to fit the electrochemical impedance spectroscopy is shown. s is the sum of the electrode and electrolyte resistances, CPE is the double layer capacitance, R ct represents the charge transfer resistance, and W s represents the Warburg impedance within the diffusion component; Fig.15D is R estimated from the equivalent circuit model s and R ct Summary of values. According to the Nyquist curve ( Figure 1 SA), it was observed that the semicircle of 1-decanethiol was much smaller than that of 1-octadecanethiol, indicating a more efficient charge transfer process at the electrode coated with the short molecules. Fig.15D It can be seen that the R calculated for the 1-decanethiol and 1-octadecanethiol system is s Almost the same, while R ct The values decrease significantly with molecular length. Similar results were observed for chiral L-ala3 and L-ala7 ( Fig. 15B and Figure 1 SD).
[0204] The inventors also examined whether chiral enhancement also occurs when the electrode is made of a material with inherently large spin-orbit coupling. The inventors used the following procedure to produce chiral thin Au films by electrodeposition in the presence of tartrate ions in the deposition solution. In brief, 0.2 mL of L-tartaric acid or DL-tartaric acid, 0.02 M Na3Au(S2O3)2, 0.42 M Na2S2O3, 0.42 M Na2SO3 were added to 10 mL of water, and the pH was adjusted to 8. Deposition was performed using a three-electrode electrochemical cell, in which a quartz substrate coated with 15 nm of Au was used as the working electrode. Saturated calomel electrode (SCE) and Pt wire were used as reference electrode and counter electrode, respectively. For deposition, a constant potential of -0.63 V was applied for 5 minutes. After electrodeposition, the electrode was washed with water and used for ORR experiments.
[0205] The handedness of the deposited chiral Au film was determined by chiral tartrate ions. Circular dichroism (CD) measurements were performed using a Chirascan spectrometer from Applied PhotoPhysics, UK. The measurement conditions for all spectra were completed under the following conditions: scanning range from 185 nm to 700 nm; 0.5 s time per point; 1 nm step size; and 1 nm bandwidth. For solution samples, a quartz cuvette with an optical path of 2 mm was used. CD spectra of Au films with L-tartaric acid or DL-tartaric acid were measured on a quartz substrate with a thickness of 0.5 mm, and Fig.16A Shown in. Fig. 16B Shown are UV-visible absorption spectra of synthesized gold (Au) films with L-tartaric acid or DL-tartaric acid.
[0206] The synthesized chiral Au thin films on quartz substrates were directly used as working electrodes for oxygen reduction reactions. For Au and Pt NPs, the same amount of chiral NPs or achiral NPs were dispersed in water by vigorous stirring and sonication. 8 μL of NP solution was dropped onto a glassy carbon electrode (GCE; 3 mm in diameter, from ALS Co., Ltd., Japan). The loading of metallic Pt was kept at 42 μg / cm 2 Geometric area (confirmed by ICP-MS). After water evaporation for 3 h at room temperature, 4 μL of 0.05 wt% Nation solution was dropped on the electrode surface to cover and stabilize the NP assembly on the electrode surface. Such NP-loaded GCE was immersed in the solution as a working electrode. ORR activity was measured at room temperature in O2-saturated 0.1 M KOH at a scan rate of 50 mV / s under oxygen purge.
[0207] The onset potential obtained with the ‘chiral gold film’ is improved compared to that of the chiral monolayer coated Au electrode, e.g. Fig. 16C As shown in Figure 3 In addition, the ORR onset potential of the chiral metal Au film is 90 mV higher than that of the film prepared with the racemic mixture of tartaric acid (in Fig. 16C For racemic Au film and chiral Au film at -0.1 mA / cm 2 The onset potentials are 0.49 V and 0.58 V, respectively), providing an enhancement factor of about 20%.
[0208] Similar enhancement due to chirality was also found in Au nanoparticles with L-cysteine or D-cysteine ( Figure 17A-Figure 17C). The synthesis of chiral gold nanoparticles was carried out according to the procedure reported in
[74] . Generally, cubic Au seeds were first synthesized and dispersed in a hexadecyltrimethylammonium bromide (CTAB) (1 mM) aqueous solution. 0.8 ml of 100 mM CTAB and 0.2 ml of 10 mM gold chloride trihydrate were added to 3.95 ml of deionized water to be used as the growth solution. The cubic seed solution was then added to the growth solution, and 100 μM cysteine was added after 20 min. The sample was placed in a 30 °C bath for 2 h, and the pink solution gradually turned blue with large scattering. The solution was centrifuged twice to remove unreacted reagents.
[0209] Fig.17A and Fig. 17B The circular dichroism spectra of synthesized gold nanoparticles (AuNPs) with L-cysteine or DL-cysteine are shown in Figure 2. Fig.17A ) and UV-visible absorption spectra ( Fig.17A ). Fig. 17C The current measured with gold nanoparticles (Au NP) of different chirality is shown relative to the potential. The curve was recorded at a scan rate of 50 mV / s in 0.1 M KOH solution saturated with O2 at room temperature. The current density was normalized to the geometric area of the GCE.
[0210] Considering the large spin-orbit coupling of Au, Fig. 17C The increased ORR onset potential of chiral Au NPs compared to achiral Au NPs, as seen in Figure 3, confirms the additional contribution of spin-polarized electrons induced by the chiral molecules. As will be shown below, this contribution must go beyond simply relaxing the spin selection rule.
[0211] In order to detect the influence of chirality on the materials used in fuel cells, the inventors synthesized platinum nanoparticles (Pt NPs) using L-enantiomers and D-enantiomers of cysteine as ligands. Platinum nanoparticles (Pt NPs) were synthesized using chloroplatinic acid hydrate and L-cysteine or DL-cysteine as ligands and water as a reaction medium. In 718 μL of E-pure water, 82 μL of 122 mM chloroplatinic acid, 200 μL of 7.5 mM L-cysteine or DL-cysteine and 200 μL of 200 mM NaBH4 were added.
[0212] Figures 18A-18D Characterization of the morphology of Pt nanoparticles (NPs) is shown, in particular, Figures 18A-18C Transmission electron microscopy (TEM) images are shown, and Fig.18B and Fig.18D The results show that the use of L-cysteine ( Fig.18A , Fig.18B ) or DL-cysteine ( Fig.18C, Fig.18D ) Size distribution of modified Pt NPs. Fig.18A and Fig.18C The scale bar in is 20 nm. TEM images were taken by using a FEI (Philips) Tecnai T12 operated at 120 kV.
[0213] For circular dichroism measurements, Fig.19A , the concentration of cysteine was increased to 50 mM. After two hours of magnetic stirring at room temperature in a N2 atmosphere, a brown transparent nanoparticle dispersion was obtained. The synthesized nanoparticles were analyzed after being fully purified by washing the NPs with E-pure water. Precipitation was accomplished by precipitation with the addition of a larger volume of isopropanol, followed by centrifugation at 10,000 rpm for 20 min. Fig.19B Shown are UV-visible absorption spectra of synthesized Pt nanoparticles (Pt NPs) with L-cysteine or DL-cysteine.
[0214] When a racemic mixture of L-cysteine and D-cysteine is used, the mixture is referred to as achiral NPs. L-cysteine-modified Pt NPs show a clear CD signal in the absorption spectrum region of the NPs, whereas racemic cysteine-modified NPs are CD silent ( Fig.19A and Fig.19B ). Similarly, the onset potential of chiral Pt NPs far exceeds that of achiral Pt NPs ( Fig.19C ). Measurements on a commercial Pt / C catalyst (nominal 20% Pt on carbon black) were also performed as a comparative benchmark.
[0215] The electrochemically active surface area (ECSA) was measured by using the hydrogen adsorption / desorption method on platinum under alkaline conditions to normalize the oxygen reduction current
[64] . A 0.1 M KOH aqueous solution was first purged with O2, and a continuous stream of argon was introduced into the cell to maintain an inert atmosphere. CV curves were recorded between 0.0 V and 1.2 V vs. RHE at a scan rate of 50 mV / s, and Figure 19D-19F The chiral Pt NPs ( Fig.19D ), achiral Pt NPs ( Fig.19E ) and commercial Pt / C catalysts ( Fig.19F ). ECSA is determined by integrating the hydrogen adsorption charge over the CV and is calculated as: ECSA = Q des / (m×Q ref ), where Q des is the total charge of H desorption, Q ref is the charge density associated with the H2 monolayer adsorption on Pt with unit weight, and m is the Pt loading on the electrode.
[0216] After normalizing the oxygen reduction current by the ECSA of each catalyst, the chiral Pt NPs show higher onset potentials than the state-of-the-art Pt / C catalysts based on the equivalent Pt mass for ORR, as shown in Figure 19G As shown in .
[0217] Previous studies have shown that the coupling of the electron spin direction to the molecular chiral axis significantly exceeds the thermal energy at room temperature
[65] and that chiral molecules act as spin filters
[66] . A measure of spin-dependent filtering is provided by the spin polarization P, which is defined as
[0218]
[0219] Among them I α is the electron current whose spin points parallel to its velocity, and I β is the current of electrons whose spins point antiparallel to their rate. The effect of chiral molecules on ORR efficiency can be revealed by probing the correlation between the length of chiral molecules and the spin polarization of electrons transported through them. Fig. 20A The dependence of spin polarization on the length of a chiral oligopeptide is shown, adapted with permission from
[67] . The conduction of electrons whose spins are aligned parallel to their velocities is higher, and the magnitude of the spin polarization increases from 30% to 45% with increasing oligopeptide length
[67] . Based on the spin polarization results, the dependence of the current during the reduction process on the spin polarization can be calculated.
[0220] Considering the ORR of L-ala3 relative to that of L-ala7, we can compare Fig. 20A The spin polarization shown in the above Figures 14A-14D (In particular, Fig. 14C and Fig.14D ) to estimate the number of electrons transferred for the oxygen reduction process. If the rate-limiting ORR step involves the transfer of a single electron, then the ratio of the spin polarizations through the two peptide films should be equal to the ratio of the observed currents through the membranes. However, if there is a multi-electron process (n electrons are transferred in the reaction step), then the ratio should be the product of the effects of each spin. This logic suggests that the following equation can be used to estimate n:
[0221]
[0222] On the left, the spin polarization (SP) of L-ala7 ala7 =45±3%) and SP ala3 =L-ala3(31±3%) and current density I ala7 and I ala3The product of represents the spin-polarized current through each film. The current density I ala7 and I ala3 By Fig. 20B In order to obtain two current densities at the same overpotential, the inventors first took the tangent at the maximum slope of the reduction current and extrapolated it to zero current density to obtain the intersection point (a and a'). From the intersection point, they then moved to a negative potential of 0.1V (b and b'). The current density at this potential is considered to be I ala7 or I ala3 (point marked with an arrow); that is, I ala7 =-0.16mA / cm 2 and I ala3 =-0.13mA / cm 2 Using these values in equation (4), the inventors found that n = 2.8. Therefore, based on the Fig. 20A Based on the spin polarization of and the equation mentioned above, the inventors concluded that 2.9±1.5 electrons are involved in the rate-determining step of the reduction process.
[0223] If we assume that the oxygen reduction reaction occurs via the four electrons (4e - ) pathway
[68] , the electron transfer number is about 2.35 based on the current density on the L-ala11 and Pt surfaces. In addition, the two-electron (2e - ) reduction [69,70], so the similar current density of Au and L-ala11 indicates that the main two-electron process occurs in the surface coated with chiral oligopeptides. This number is consistent with the results calculated by the inventors above based on spin polarization.
[0224] The calculations therefore imply that 2.9 ± 1.5 electrons are involved in the rate-determining step of the reduction; a similar number of electrons was obtained by evaluating the current density between the Pt surface and the chiral monolayer ( Fig.12 ). This finding suggests that when the monolayer modified Au surface is used as a working electrode, oxygen reduction occurs via a two-electron mechanism as described above (Eq. (2) above).
[0225] Regardless of the exact mechanism of oxygen reduction, it requires at least two electrons to produce O2 in the first stage 2- or HO2 -
[62] When considering spin statistics, it is important to consider the projection of the O2 molecule spin onto the chiral axis from the molecular layer when the O2 molecule approaches the SAM. Fig. 20C Figure 2 shows the spin splitting of triplet oxygen when it interacts with a spin-polarized electron residing on a chiral molecule. For O2, with its unpaired electrons 1 and 2, the three possible spin states are α(1)α(2), β(1)β(2), and is possible. In the case of chiral oligopeptides, the two electrons injected from the monolayer have the same spin projection on the molecular axis, i.e. their state will be αα. The reaction barrier is therefore influenced by an entropic factor (related to spin statistics) and an enthalpy factor caused by the stabilization of the β(1)β(2) state of O2 by spin exchange interactions with the polarized electrons on the chiral molecule.
[0226] Fig.20D and Fig.20E It is shown that in the chiral system ( Fig.20D ) and in the case of achiral systems ( Fig.20E ). In the case of an achiral system, the two electrons can have four possible configurations, only one of which leads to a reaction. In a chiral system, there is only one possible configuration, and since this is the only configuration that can lead to a reaction, the electrons are strongly coupled to the molecular framework.
[0227] While in chiral molecules the spin orientation is defined relative to the molecular axis, on oxygen the three degenerate spin states split when the molecule approaches a chiral monolayer; that is, its spin states split, just as in the case of a magnetic field, and the states β(1)β(2) stabilize. When oxygen interacts with the chiral monolayer (electron cloud overlap), the strength of these interactions grows due to the spin exchange effect ( Fig. 20C ). This effect reduces the enthalpy barrier and results in more efficient injection of spins from the monolayer into the oxygen system. In addition, the alignment of the O2 spin states with the chiral film reduces the entropic contribution to the free energy barrier ( Fig.20D and Fig.20E ). For the achiral film, there are four possible spin states in the monolayer αα, ββ, αβ, and βα, only one of which will enable efficient electron transfer to oxygen (hence the reaction probability is only 1 / 4). Furthermore, since the spins on the achiral monolayer are not coupled to the molecular framework, they will not split the spin state of oxygen and the enthalpy barrier will not be reduced.
[0228] Model calculations support the mechanism described above. Theoretical simulations treat chiral molecules as a series of nuclear sites, each of which hosts a single electronic energy level and is coupled to both its nearest and next nearest neighbors via both elastic and inelastic spin-orbit interactions [70,71].
[0229] The inelastic components in this model include nuclear vibrations that are coupled to the electronic structure through both spin-independent electron-vibration coupling and spin-dependent electron-vibration coupling. These two components originate from nuclear motions that change the nuclear confinement potential and are therefore related to both the overlapping matrix elements involved in the tunneling rate between the nuclei and the spin-orbit interactions in the structure. Theoretical simulations were performed using a chiral molecular model based on a chain of nuclear sites, each of which hosts a single electron energy level (ε m ), and couples to its nearest-neighbor nuclear site via both elastic hopping (t0) and inelastic hopping (t1), and couples to its next-nearest-neighbor nuclear site via both elastic spin-orbit interaction (λ0) and inelastic spin-orbit interaction (λ1), see Refs. (24) and (25). The inelastic component in this model consists of nuclear vibrations (mode ω) coupled to the electronic structure via both spin-independent electron-vibration coupling (t1) and spin-dependent electron-vibration coupling (λ1). m ). These two components arise from nuclear motions that change the nuclear confinement potential V(r) and are therefore related to both the overlapping matrix elements involved in the tunneling rate between the nuclei and the spin-orbit interactions in the structure.
[70] and
[71] , while the opposite end is directly connected via the form The direct exchange interaction v is connected to the O2 molecule, where represents the creation (annihilation) spinor at the molecular site N, and σ is a vector of Pauli matrices, and is the spin operator of the O2 molecule, where S 1,2 represents the spin 1 / 2 operator for two unpaired electrons. The exchange integral v is calculated as a function of the distance R between the chiral molecule and the O2 molecule by using the exchange expression between the electrons in the H2 molecule,
[0230]
[0231] where j0 = e 2 / 4πε0, e is the electron charge, ε0 is the vacuum permittivity, S′(s)=-S(s), s=R / a0, a0 is the Bohr radius, γ is the Euler constant, and E1(x) is the exponential integral.
[0232] For simulations, the inventors have simulated chiral molecules with six turns, eight ions per turn, and parameters (in terms of t0=40 meV), where μ is the total chemical potential of the system, and Γ0 represents the coupling strength between the metal reservoir and the chiral molecule. All simulations were done at T=300K, as summarized in Table 4 below:
[0233]
[0234] Table 4
[0235] One end of the chiral molecule is attached to the metal reservoir, and the opposite end interacts with the O2 molecule through a direct exchange interaction v, which is calculated as a function of the distance R between the chiral molecule and the O2 molecule using the exchange expression between electrons in the H2 molecule (see the description below). Fig.20F )
[70] . The exchange interaction is in represents the creation (annihilation) spinor at the molecular site N, σ is the vector of the Pauli matrix, and is the spin operator of the O2 molecule. The assembly of metal, chiral molecule and O2 molecule constitutes an open system, in which the charge distribution and accompanying spin polarization of the chiral molecule and the magnetic moment of the O2 molecule are determined in a self-consistent computation using a non-equilibrium green function. Fig.12 F shows the effect of the helical interaction on the spin substate energies of the O2 molecule by showing the calculated triplet energy levels of oxygen presented as a function of the distance between the chiral molecule and oxygen.
[0236] Although a simple model, the calculations show a splitting of the triplet sublevels that can be hundreds of meV (tens of kcal / mol). These findings are consistent with recent work showing enhanced oxygen reduction efficiency using magnetic electrodes [72, 73], which may be due to the spin alignment of the injected electrons. As long as the second electron is injected on a time scale shorter than the spin depolarization time, the proposed mechanism should be relevant for simultaneous two electron reduction as well as a sequential process.
[0237] Given that the CISS effect can enhance the rates of multi-electron reaction steps by reducing the number of accessible spin channels, it is interesting to speculate on its effects on the glucose oxidation process, which involves 6 oxygen molecules and 24 electrons. In the case of such a complex redox scheme where there may be a large number of multi-electron transfer steps, the reduction in activation entropy through spin filtering can increase the overall rate of chiral biomolecules by multiple orders of magnitude. Homochirality in biological organisms represents an entropic reduction that increases the Gibbs free energy of the organism. This may be a strong benefit of the respiratory process and from homochirality, as the smaller number of possible spin states (lower entropic reaction barrier) helps drive this selection. This new mechanism in which spin-filtered electrons enhance overall reaction efficiency may partially explain why life has so consistently maintained chirality during evolution.
[0238] The present disclosure demonstrates that controlling spin in a multi-electron transfer process such as ORR results in two contributions to the reaction rate. The first is a correspondence with a spin-selective constraint, allowing the reaction to occur on a triplet potential energy surface. The second is a reduction in the number of states available for the reaction, thereby reducing the entropic barrier. The present results suggest that control of electron spin is an important attribute for catalysts used in important oxygen-related reactions, and it reduces overpotential and increases current density.
[0239] refer to Fig.21, shows a possible configuration of an energy storage device 500, which includes an electrochemical cell configured as a battery 502. Battery 502 includes, among other things, an electrode 504A and a counter electrode 504B. Each of electrodes 504A and 504B includes a respective substrate 506A and 506B having a conductive surface and carrying a respective chiral system 508A and 508B. Chiral system 508A and / or 508B may be at least one of an organic substance and an inorganic substance having a chiral property. As described above, the chiral induced spin selectivity (CISS) effect enables the resistance of the electrode interface to be reduced by arranging the electron spin and significantly reduces the overpotential required for the chemical process. When electrons flow from one material to another in a battery cell, the spin of such electrons has an effect on the work function and the internal resistance. The reduction of the work function and the internal resistance of batteries and battery components is an important aspect in the overall performance of the battery. In particular, reducing the internal resistance of such an energy storage device can lead to more efficient electrochemical reactions, reduce resistivity waste, and improve energy storage device performance (e.g., capacity, charging time, reduced temperature, etc.). The battery can be a rechargeable battery or a disposable battery. In this specific and non-limiting example, the electrode 504A is configured to interact with the first electrolyte 510A of the battery 502, and the counter electrode 504B is configured to interact with the second electrolyte 510B, which interacts with the first electrolyte. If the first electrolyte and / or the second electrolyte 510A and 510B are solid, the electrode 504A and the counter electrode 504B are placed in contact with each electrolyte. If the first electrolyte and / or the second electrolyte 510A and 510B are liquids, the electrode 504A and the counter electrode 504B are immersed in each electrolyte. In this case, the first electrolyte and the second electrolyte 510A and 510B are fluidly connected to each other. The two electrolytes can be made of the same material. However, the configuration of the battery is not limited to such a configuration, and the electrodes 504A and 504B can be immersed in the same electrolyte. The interaction between the chiral electrode and the electrolyte is configured to change the spin state at the electrode-electrolyte interface in order to optimize the operation of the battery. In this specific and non-limiting example, the electrolytes 510A and 510B are separated by a permeable (e.g., porous) membrane / diaphragm 512, which prevents them from mixing, but provides chemical communication between the electrolytes 510A and 510B, i.e., allows ions to diffuse through to maintain the electrical neutrality of the battery 502.
[0240] The battery 502 further includes an electrical module 514 for applying a potential difference between the electrode 504A and the counter electrode 504B for at least one of charging and discharging the energy storage device 500 .
[0241] Chiral systems 508A and 508B are configured to control the work function of the corresponding electrodes 504A and 504B. The interaction between the chiral system and the electrodes causes charge rearrangement, spin polarization of the corresponding surfaces 508AS and 508BS, and spin polarization of electrons injected from or to the corresponding surfaces 508AS and 508BS, so as to reduce the work function of the corresponding electrodes 504A and / or 504B, the potential for starting the electrochemical process, and the electrical internal resistance of the electrodes.
[0242] exist Fig.21 In the non-limiting example of , the left electrode 504A is positive, indicating that electrons are injected into the surface, and the right counter electrode 504B is negative, indicating that electrons are injected from the surface. The energy storage device 500 is configured to reduce the potential difference applied by the electrical module 514 between the electrode 504A and the counter electrode 504B for at least one of charging and discharging the energy storage device 500 due to the interaction between the chiral systems 508A and 508B and the corresponding electrode substrates 506A and 506B causing charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected into or from the corresponding surfaces 508AS and 508BS.
[0243] refer to Fig. 22 , shows a possible configuration of a photovoltaic cell module 600, which includes at least one photovoltaic cell 602, which is configured and operable to receive light, convert the energy of the received light into electrical energy and generate electricity. Photovoltaic cell 602 includes, in particular, a pair of electrodes / collectors 604A and 604B, which electrically couple photovoltaic cell 602 and are configured and operable to collect electricity. Photovoltaic cell 602 also includes top and bottom connecting layers 608A and 608B, respectively, an absorption layer 610 (made of semiconductor material) and an anti-reflection layer 612. External circuit 614 provides current generated by excited electrons generated in photovoltaic cell 602. In this specific and non-limiting example, each of electrodes 604A and 604B includes a corresponding layer 606A and 606B, which has a conductive surface that at least partially carries a chiral system. However, the configuration of photovoltaic cell module 600 is not limited to this configuration.The coating having the chiral system may be applied to electrodes 604A and 604B as in this example, or to tie layers 608A and 608B, or to both electrodes and tie layers.
[0244] During typical operation of photovoltaic cell 602, when light falls on the solar cell, electrons in absorber layer 610 are excited from a lower energy "ground state" in which the electrons bind to specific atoms in the solid to a higher "excited state" in which the electrons can move through the solid. The junction-forming layers 608A and 608B induce a built-in electric field that provides collective motion for the electrons to flow through electrical contact layers 604A and 604B into external circuit 614, where they can do useful work.
[0245] The electron-hole recombination rate is one of the key factors in photovoltaic cell efficiency and presents a loss mechanism in the active region. Another loss mechanism is caused by the overpotential barrier that the charge needs to pass through before entering the electrode / current collector 604A and 604B. Layers 606A and 606B, respectively placed between the bonding layers 608A and 608B and the metal electrodes / current collectors 604A and 604B, are configured and operable to enhance the performance of the photovoltaic cell module by reducing the electrode overpotential at the current collector and improving the charge separation efficiency while reducing the recombination losses.
[0246] refer to Fig.23A and Fig. 23B , showing a possible configuration of an electrical component comprising a substrate having a conductive surface at least partially carrying a chiral system. Fig.23A A junction field effect transistor (JFET) 700 is shown with a chiral coating 702 covering the electrodes of the gate, source and drain terminals. Fig. 23B An interconnect 750 is shown including a metal layer, a magnetic layer, or a superconductor layer 710 and two contacts / electrodes 712, wherein a chiral coating 702 lines the interface between the outer surface of the metal layer, the magnetic layer, or the superconductor layer 710 and the contacts / electrodes 712. In both components (700 and 750), the chiral system 702 is configured to control the work function of the electrical component, and the interaction between the chiral system 702 and the corresponding surfaces of the electrodes causes charge rearrangement, spin polarization of the surfaces, and spin polarization of electrons injected from or into the electrode surfaces so as to reduce the work function of the electrical component and the electrical internal resistance of the electrical component. It should be noted that the chiral coating 702 can be applied to the electrodes of the gate terminal, the source terminal, and the drain terminal, as shown in FIG. Fig.23A In the example of , it is applied to the semiconductor substrate in contact with the corresponding electrode, or to both the electrode and the semiconductor substrate. Fig. 23B In an example, chiral coating 702 can be applied to the surface of contact / electrode 712, or to the outer surface of layer 710, or to both the electrode and the layer. JFET 700 can be configured as an electrical switch to control the current flow of an energy source, and interconnect 750 can be configured to electrically couple multiple circuits.
[0247] refer to Fig.24A and Fig. 24B , shows possible configurations of energy storage devices 900 and 950, which are configured as electrochemical capacitors. Fig.24A The electrochemical capacitor 900 includes two electrodes 902A and 902B separated by an ion-permeable membrane (diaphragm) 904, an electrolyte 906 ionically connecting the two electrodes, and a power source 908. When the electrodes are polarized by an applied voltage 908, the ions in the electrolyte 906 form an electric double layer 910A and 910B of opposite polarity to the polarity of the corresponding electrode. For example, a positively polarized electrode will have a negative ion layer at the electrode / electrolyte interface, and a charge balance layer of positive ions adsorbed onto the negative electrode layer. The opposite is true for negatively polarized electrodes. The double layers 910A and 910B are approximately used as dielectric layers in conventional capacitors, and the efficiency of charging and discharging these electric double layers directly affects the capacitance achieved by the storage device 900.
[0248] According to some embodiments of the novel technology of the present disclosure, each of the electrodes 902A and 902B is coated with a chiral system 912, which is configured to cause a reduction in the potential difference applied between the electrodes 902A and 902B for at least one of charging and discharging the energy storage device 900 due to the interaction between the chiral system 912 and the corresponding electrode, causing charge rearrangement, spin polarization of the electrode surface, and spin polarization of electrons injected into or from the electrode surface. Alternatively or additionally, the ion permeable membrane (membrane) 904 may include a substrate having a conductive surface that at least partially supports the chiral system. The chiral membrane can enhance charge separation due to the spin filtering effect
[66] . Therefore, in order to enhance charge separation, the energy storage device of the present disclosure may include a chiral electrode and / or at least one chiral membrane.
[0249] Fig. 24BThe electrochemical capacitor 950 includes two charged conductive plates 952A and 952B, one plate (e.g., 952A) is positively charged and one plate (e.g., 952B) is negatively charged. The capacitor 950 also includes a dielectric 954 and a connecting line 956 that carries the current generated and used to charge / discharge the capacitor 950. The dielectric 954 operates as a diaphragm separating the negative and positive charges of the two charged conductive plates 952A and 952B. According to some embodiments of the novel technology of the present disclosure, each of the conductive plates 952A and 952B is coated with a chiral system 958, which is configured to cause a reduction in the potential difference applied between the conductive plates 952A and 952B for at least one of charging and discharging the energy storage device 950 due to charge rearrangement, spin polarization of the surface of the corresponding conductive plate, and spin polarization of electrons injected into or from the corresponding surface due to interaction between the chiral system 958 and the corresponding conductive plate.
[0250] refer to Fig.25A and Fig.25B , respectively, show two possible configurations of electrochemical cell systems 1000 and 1100. In this specific and non-limiting example, Fig.25A The electrochemical system 1000 includes an electrochemical cell 1010 configured as a water electrolyzer, wherein electricity is used to decompose water into oxygen and hydrogen by electrolysis, for example, by applying a voltage through a power source 1014. However, the electrochemical cell system of the present disclosure is not limited to such a configuration, and another solid or liquid electrolyzer may be used instead. In this example, the hydrogen released in this manner can be used as a hydrogen fuel, or remixed with oxygen to produce a hydrogen-oxygen mixed gas for welding and other applications. The electrodes of the electrochemical cell 1000, namely the anode 1012A and the cathode 1012B, are configured according to the principles of the present disclosure. The two electrodes 1012A and 1012B carry a chiral system 1016 as described in the present disclosure, and can be immersed in water, in which water is used as an electrolyte in this specific and non-limiting example. The electrolyte can also be solid, so that the electrode is placed in contact with the solid electrolyte. The interaction between the chiral electrode and water is configured to change the spin state at the electrode-electrolyte interface so as to optimize the operation of the electrochemical system 1010. Fig.25BThe electrochemical system 1100 includes an electrochemical cell configured as a fuel cell 1110 that converts the chemical energy of a fuel into electricity. The fuel cell 1110 includes, among other things, two electrodes, an anode 1112A and a cathode 1112B; an electrolyte 1116 that is specifically designed so that ions can pass through it but electrons cannot; and a load 1114 that carries the current generated in the fuel cell 1110. The electrodes 1112A and 1112B of the fuel cell 1110 are configured according to the principles of the present disclosure. The two electrodes 1112A and 1112B carry a chiral system 1118 as described in the present disclosure. The interaction between the chiral electrodes 1112A and 1112B and the electrolyte 1116 is configured to change the spin state at the electrode-electrolyte interface in order to optimize the operation of the electrochemical system 1100.
Claims
1. A method for controlling the work function of at least one surface, the method comprising: measuring a first work function of the first surface; depositing a chiral system on the first surface to induce a change in the first work function; applying a potential difference between the first surface and the second surface so as to generate charge transfer between the first surface and the second surface; measuring a second work function of the first surface carrying the chiral system; wherein the second work function is lower than the first work function, and The interaction between the chiral system and the first surface is configured to cause charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected from or into the first surface, thereby changing the work function of the first surface. 2 . The method of claim 1 , wherein depositing the chiral system on the first surface comprises chemically binding the chiral system to the first surface or physically adsorbing the chiral system on the first surface.
3. The method according to claim 1 or claim 2, wherein the chiral system comprises at least one of an organic substance and an inorganic substance having a chiral property.
4. The method according to claim 3, wherein the chiral system comprises at least one of the following chiral organic materials or the following chiral inorganic materials, the chiral organic material is: polypeptide, oligopeptide, amino acid, protein, DNA, helicene, chiral polymer or any combination thereof, the chiral inorganic material is: chiral oxide, chiral metal and chiral crystal or any combination thereof.
5. The method according to any one of claims 1 to 4, wherein the chiral system is configured as a monolayer structure or a multilayer structure, which operates as a layer for improving charge separation.
6. The method of claim 5, wherein the chiral system comprises a self-assembled monolayer of chiral molecules or chiral biomolecules.
7. A method according to any one of claims 1 to 6, wherein when the first surface is configured as an electrode and can be operated as an electrode and the second surface is configured as a counter electrode and can be operated as a counter electrode, the method also includes causing at least one chiral coated surface to interact with an electrolyte to serve as an electrode and causing the other surface to interact with an electrolyte to serve as a counter electrode before applying the potential difference, and the interaction between the chiral electrode and the electrolyte is configured to change the spin state at the electrode-electrolyte interface.
8. An electrode for an electrochemical process, the electrode comprising a substrate having a conductive surface at least partially carrying a chiral system, wherein the chiral system is configured to control the work function of the electrode, and the interaction between the chiral system and the electrode causes charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected from or into the surface, so as to reduce the work function of the electrode, the potential for starting the electrochemical process, and the electrical internal resistance of the electrode. 9 . The electrode according to claim 8 , wherein the chiral system comprises at least one of an organic substance and an inorganic substance having a chiral property.
10. The electrode according to claim 8 or 9, wherein the chiral system comprises at least one of the following chiral organic materials or the following chiral inorganic materials, the chiral organic material is: polypeptide, oligopeptide, amino acid, protein, DNA, helicene, chiral polymer or any combination thereof, the chiral inorganic material is: chiral oxide, chiral metal and chiral crystal or any combination thereof.
11. The electrode according to any one of claims 8 to 10, wherein the chiral system is configured as a single layer structure or a multilayer structure.
12. The electrode of claim 11, wherein the chiral system comprises a self-assembled monolayer of chiral molecules.
13. The electrode according to any one of claims 8 to 12, wherein the chiral system is chemically bound to the surface of the substrate or physically adsorbed on the surface of the substrate.
14. The electrode according to any one of claims 8 to 12, wherein the substrate is made of at least one of a metal, a chiral conductor and a semiconductor.
15. The electrode according to any one of claims 8 to 14, configured as a light absorber.
16. The electrode of claim 10, wherein the substrate is configured as a light absorber.
17. An electrode according to claim 10 or 11, comprising at least one layer of light absorber carried by the substrate.
18. The electrode according to any one of claims 10 to 12, wherein the chiral system comprises at least one layer of a light absorber having chiral properties.
19. An electrode according to any one of claims 10 to 13, comprising light absorbing nanoparticles bound to the substrate via the chiral system.
20. A method of using an electrode according to any one of claims 8 to 19 in an electrochemical system, the method comprising interaction between the electrode and an electrolyte of the electrochemical system and passing current from the electrode into the electrolyte to cause charge rearrangement, spin polarization of the surface and spin polarization of electrons injected into or from the surface, thereby reducing the work function of the chiral electrode, the interaction between the chiral electrode and the electrolyte being configured to change the spin state at the electrode-electrolyte interface to optimize the operation of the electrochemical system.
21. An electrochemical cell system, comprising an electrochemical cell and an electrode according to any one of claims 8 to 20, wherein the electrochemical cell is configured to electrolyze at least a first electrolyte or convert chemical energy of a fuel into at least one of electricity, wherein the electrode carries the chiral system and is configured to interact with the first electrolyte, and the interaction between the chiral electrode and the first electrolyte is configured to change the spin state at the electrode-electrolyte interface so as to optimize the operation of the electrochemical system.
22. The electrochemical cell system of claim 21, further comprising a counter electrode connectable to the chiral electrode and configured to interact with a second electrolyte in chemical communication with the first electrolyte, wherein an electrical potential energy can be applied between the chiral electrode and the counter electrode.
23. The electrochemical cell system of claim 22, wherein the counter electrode comprises a substrate having a conductive surface at least partially carrying a chiral system.
24. The electrochemical cell system of claim 23, wherein the chiral system comprises at least one of an organic substance and an inorganic substance having a chiral property.
25. The electrochemical cell system of claim 24, wherein the chiral system comprises at least one of the following chiral organic materials or the following chiral inorganic materials, wherein the chiral organic material is: polypeptide, oligopeptide, amino acid, protein, DNA, helicene, chiral polymer or any combination thereof, and the chiral inorganic material is: chiral oxide, chiral metal and chiral crystal or any combination thereof.
26. The electrochemical cell system according to any one of claims 22 to 25, wherein the chiral system is configured as a single layer structure or a multilayer structure.
27. The electrochemical cell system of claim 26, wherein the chiral system comprises a self-assembled monolayer of chiral molecules.
28. The electrochemical cell system of any one of claims 22 to 27, wherein the chiral system is chemically bound to the surface of the substrate or physically adsorbed on the surface of the substrate.
29. The electrochemical cell system of any one of claims 22 to 28, wherein the substrate is made of at least one of a metal, a chiral conductor, and a semiconductor.
30. The electrochemical cell system of any one of claims 22 to 29, wherein the first electrolyte and the second electrolyte are made of the same material.
31. The electrochemical cell system of any one of claims 22 to 30, further comprising a membrane configured to create a separation between the first electrolyte and the second electrolyte.
32. The electrochemical cell system of claim 31, wherein the membrane comprises a substrate having a conductive surface at least partially carrying a chiral system.
33. The electrochemical cell system of claim 32, wherein the chiral system comprises at least one of an organic substance and an inorganic substance having a chiral property.
34. The electrochemical cell system of claim 32 or 33, wherein the chiral system comprises at least one of the following chiral organic materials or the following chiral inorganic materials, wherein the chiral organic material is: a polypeptide, an oligopeptide, an amino acid, a protein, a DNA, a helicene, a chiral polymer or any combination thereof, and the chiral inorganic material is: a chiral oxide, a chiral metal and a chiral crystal or any combination thereof.
35. The electrochemical cell system according to any one of claims 32 to 34, wherein the chiral system is configured as a single layer structure or a multilayer structure.
36. The electrochemical cell system of claim 35, wherein the chiral system comprises a self-assembled monolayer of chiral molecules.
37. The electrochemical cell system of any one of claims 32 to 36, wherein the chiral system is chemically bound to the surface of the substrate or physically adsorbed on the surface of the substrate.
38. The electrochemical cell system of any one of claims 32 to 37, wherein the substrate is made of at least one of a metal, a chiral conductor, and a semiconductor.
39. An electrochemical cell system according to any one of claims 21 to 38, configured to be immersed in a solution containing oxygen and operable to enhance electron transfer from the electrode to oxygen and reduce the overpotential of the oxygen reduction reaction.
40. An energy storage device, comprising at least one electrochemical cell according to any one of claims 21 to 39, an electrical module for applying a potential difference between the electrode and a counter electrode connectable to the electrode for at least one of charging and discharging the energy storage device, wherein the energy storage device is configured to cause a reduction in the potential difference applied between the electrode and the counter electrode for at least one of charging and discharging the energy storage device due to charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected into or from the surface caused by interaction between the chiral system and the electrode.
41. The energy storage device of claim 22 or 40, wherein at least one of the first electrolyte and the second electrolyte comprises an active material that is a chiral material.
42. The energy storage device of claim 32, configured as a battery.
43. The energy storage device of claim 32, configured as an electrochemical capacitor.
44. A photovoltaic cell module, comprising at least one photovoltaic cell, the at least one photovoltaic cell being configured and operable to receive light, convert the energy of the received light into electrical energy and generate electricity; at least one pair of electrodes, the at least one pair of electrodes being electrically coupled to the photovoltaic cell and being configured and operable to collect the electricity; and a layer having a conductive surface that at least partially carries a chiral system, the layer being placed between the at least one photovoltaic cell and the at least one pair of electrodes, and being configured and operable to enhance the performance of the photovoltaic cell module.
45. The photovoltaic cell module of claim 44, wherein at least one electrode comprises a substrate having a conductive surface at least partially carrying a chiral system.
46. The photovoltaic cell module according to claim 45, wherein the chiral system comprises at least one of an organic substance and an inorganic substance having a chiral property.
47. The photovoltaic cell module according to claim 46, wherein the chiral system comprises at least one of the following chiral organic materials or the following chiral inorganic materials, the chiral organic material is: polypeptide, oligopeptide, amino acid, protein, DNA, helicene, chiral polymer or any combination thereof, the chiral inorganic material is: chiral oxide, chiral metal and chiral crystal or any combination thereof.
48. The photovoltaic cell module according to any one of claims 45 to 47, wherein the chiral system is configured as a single-layer structure or a multi-layer structure.
49. The photovoltaic cell module of claim 48, wherein the chiral system comprises a self-assembled monolayer of chiral molecules.
50. The photovoltaic cell module according to any one of claims 45 to 49, wherein the chiral system is chemically bound to the surface of the substrate or physically adsorbed on the surface of the substrate.
51. The photovoltaic cell module according to any one of claims 45 to 50, wherein the substrate is made of at least one of a metal, a chiral conductor and a semiconductor.
52. An electrical component, comprising a substrate having a conductive surface at least partially carrying a chiral system, wherein the chiral system is configured to control the work function of the electrical component, and the interaction between the chiral system and the electrical component causes charge rearrangement, spin polarization of the surface, and spin polarization of electrons injected from or into the surface, so as to reduce the work function of the electrical component and the electrical internal resistance of the electrical component.
53. The electrical component of claim 52, wherein the chiral system comprises at least one of an organic substance and an inorganic substance having a chiral property.
54. An electrical component according to claim 52 or 53, wherein the chiral system comprises at least one of the following chiral organic materials or the following chiral inorganic materials, the chiral organic material is: polypeptide, oligopeptide, amino acid, protein, DNA, helicene, chiral polymer or any combination thereof, the chiral inorganic material is: chiral oxide, chiral metal and chiral crystal or any combination thereof.
55. The electrical component of any one of claims 52 to 54, wherein the chiral system is configured as a single layer structure or a multilayer structure.
56. The electrical component of claim 55, wherein the chiral system comprises a self-assembled monolayer of chiral molecules.
57. The electrical component of any one of claims 52 to 56, wherein the chiral system is chemically bound to the surface of the substrate or physically adsorbed on the surface of the substrate.
58. The electrical component of any one of claims 52 to 57, wherein the substrate is made of at least one of a metal, a chiral conductor, and a semiconductor.
59. An electrical component according to any one of claims 52 to 58, configured as an electrical switch, the electrical switch being configured to control the current flow of an energy source.
60. The electrical component of any one of claims 52 to 59, configured as an electrical connector configured to electrically couple a plurality of circuits.
Citation Information
Patent Citations
Non-vacuum methods for the fabrication of organic semiconductor devices
US20050019976A1
Rotary engines
US3250260A
Method for manufacturing an electrode
WO2008127111A1
Dopant injection layers
WO2013019993A1